Micro-FTIR identifies osteodifferentiation markers in heterogeneous mesenchymal stem cell populations - João T.S. Martins; Clara Martins; João A. Rodrigues; Inês C.R. Graça; Daniela S. Bispo; Ana L.M. Batista de Carvalho; Brian J. Goodfellow; João F. Mano; Mariana B. Oliveira; Mariela M. Nolasco; Maria P.M. Marques; Paulo J.A. Ribeiro-Claro; et al. (Analytica Chimica Acta, 2026)

The Missing Branches of the Bee Tree of Life: Addressing Global Darwinian Shortfalls and Their Drivers - Felipe Walter Pereira; Matheus Lima Araujo; Anderson Lepeco; Bruno Ferreira Marques; Hugo Bampi; Lucas Jardim; Luísa Vareira; Luisa G. Carvalheiro; Thiago F. Rangel; José Alexandre F. Diniz Filho (Journal of Biogeography, 2026)
Aim Estimate the Darwinian shortfall (i.e., the lack of knowledge about phylogenetic relationships) of bees worldwide, as well as identify their drivers. Location Global. Taxon Bees (Hymenoptera, Anthophila). Methods We built phylogenies for over 12,000 bee species, combining the most comprehensive phylogeny and an algorithm with random solutions to insert missing lineages. The Darwinian shortfall was quantified as the Phylogenetic Diversity (PD) deficit, the ratio of inserted branch lengths at the assemblage level. We identified potential ecological and socioeconomic drivers of the Darwinian shortfall using Simultaneous Autoregressive (SAR) models. Results The highest shortfalls were identified in the Southern Hemisphere. Mean species range size and species richness were the strongest drivers, as smaller ranges and higher richness were associated with higher deficits. Per capita GDP was negatively associated with PD deficits, while population and road densities showed positive but weak effects. Sample completeness had a weaker effect, limited by missing occurrence data in many regions. Main Conclusions Our findings underscore the need for integrative efforts combining taxonomy, data digitization, adequate research investments, and targeted sampling, especially in the Global South. Overcoming the Darwinian shortfall is essential to develop robust strategies to preserve the Tree of Life, especially for one of the most important groups of pollinators while facing the ongoing biodiversity crisis.

Er and Er/Yb doped TiO2 solar-light-active photocatalysts for minocycline removal from water and wastewaters: Effect of synthesis and immobilization into MICROSCAFS® - Sofia Moreira Fernandes; Beatriz Trindade Barrocas; Ana Maria Ferraria; Luís F. Santos; M. Conceição Oliveira; Markus Niederberger; Ana C. Marques (Chemosphere, 2026)

Combating heat stress through urban planning: Integrated case studies for Lisbon and Islamabad - Niels Souverijns; Dirk Lauwaet; Tiago Capela Lourenço; Inês Gomes Marques; Fahad Saeed; Mariam Saleh Khan; Khadija Irfan; Sarantis Georgiou; Raluca Davidel; Miechel De Paep; Séverine Hermand; Chahan M. Kropf; et al. (Landscape and Urban Planning, 2026)

Effect of supplementation with different trace minerals sources and fibrolytic enzyme on the productive and reproductive performance of Nellore cows on pasture - Keuven S. Nascimento; Amanda C. M. Queiroz; Aline N. Rodrigues; Luiz F. Costa e Silva; Carlos R. Zilioti; James E. Pettigrew; Rodrigo S. Marques; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2026)

Biological performance of Melanaphis sorghi (Theobald, 1904) (Hemiptera: Aphididae) on different host plants - D. G. Santos; K. A. S. Rezende; T. F. Silva; B. L. Silva; V. M. Marques; N. M. Santos; P. S. Pereira; F. D. Tardin; A. M. Auad; M. L. F. Simeone; S. M. Mendes (Phytoparasitica, 2026)
The sorghum aphid, Melanaphis sorghi (Theobald, 1904) (Hemiptera: Aphididae), is a significant pest. This study classified the host suitability of seven Poaceae genotypes: commercial and wild sorghum ( S. bicolor , S. sudanense , S. bicolor verticilliflorum ), pearl millet ( Pennisetum glaucum ), and maize ( Zea mays ). Aphid biological performance was assessed via leaf-disc bioassays under controlled conditions (24 ± 2 °C, 60 ± 10% RH). Infestation progression and plant injury were evaluated in greenhouse trials. Plant cell wall composition was analyzed using NIRS spectroscopy. Results established a clear host suitability gradient. All Sorghum genotypes were suitable hosts, supporting positive population growth. The commercial hybrid AG1090 exhibited the highest net reproductive rate (R₀ = 16.17). Pearl millet and maize were non-hosts, with reproduction virtually absent (R₀ ≤ 0.08). Greenhouse data confirmed this pattern, with sorghum genotypes (e.g., S. sudanense , S. bicolor verticilliflorum ) reaching infestation levels above 84%, while pearl millet and maize remained below 24% with no visible injury. Statistical analysis revealed that plant susceptibility was positively correlated with leaf hemicellulose content. Principal Component Analysis (PCA) segregated susceptible sorghum genotypes from the non-host species based on this biochemical factor. It is concluded that pearl millet and maize are not hosts for M. sorghi . The cell wall composition, specifically hemicellulose content, is a key factor influencing aphid infestation levels. These findings provide a basis for developing sorghum cultivars with reduced susceptibility.

Olfactory bulb 6-OHDA neurotoxicity as a model of early cortical dysfunction - Edson Fiorenza-Neto; Bruna B. Gattiboni; Karin Almeida; Luis F. Marqueze; Bassam F. Mogharbel; Juliana R. N. de Aguiar; Larissa C. Marques; Larissa R. Lazarini; Stephanie R. S. Carvalhal; Angelica Boldt; Ricardo C. Cunha; Katherine A. T. Carvalho; et al. (Molecular and Cellular Biochemistry, 2026)
The olfactory bulb (OB) is one of the earliest brain regions affected in neurodegenerative diseases such as Parkinson’s disease (PD). Its high metabolic rate, dopaminergic modulation, and connectivity with the cortical and limbic regions make it particularly vulnerable to early neuroinflammatory and oxidative processes. This study aimed to investigate whether the administration of 6-hydroxydopamine (6-OHDA) into the OB induces behavioral, redox, and inflammatory alterations associated with early cortical disturbances. Male Wistar rats were randomly assigned to the sham or 6-OHDA groups and underwent stereotaxic injection of the vehicle or 6-OHDA into the left OB. Behavioral performance was assessed in the open-field test 12 days after surgery, and cortical tissue was collected for biochemical and molecular analyses. Cytokines (IL-1β, IL-6, TNF-α, IL-10, IFN-γ, and MCP-1) were quantified by Luminex, redox parameters (CAT, GPx, MDA, and protein carbonyls) by spectrophotometry, and neuronal signaling proteins (c-FOS, CREB, and BDNF) by qPCR. Animals with 6-OHDA lesions exhibited decreased latency and increased time spent in the central zone of the open field, indicating altered exploratory behavior. IL-6 levels were significantly elevated, whereas IFN-γ was reduced in the cortex, while IL-1β, TNF-α, MCP-1, and IL-10 remained unchanged. The oxidative stress markers MDA and protein carbonyls were increased, while catalase and glutathione peroxidase activities showed no change. The expression of c-FOS, CREB, and BDNF was not significantly modified. These findings indicate that localized 6-OHDA administration in the OB is sufficient to elicit behavioral, inflammatory, and oxidative alterations in connected cortical regions, which may resemble early non-motor features associated with olfactory dysfunction, without representing a neurodegenerative disease-specific process.

Demonstration of an electrochemical mobile CO₂ capture and utilization system: Design and implementation at industrial sites - H. Fatoorehchi; S.H.B. Vinjarapu; S. Vallejo-Castaño; U.D. Bihlet; S. Borgquist; T.L. Biel-Nielsen; R. Neerup; F. Shaahmadi; M. Demeter; I. Györbiró; P. Bountzis; M. Shi; et al. (Journal of Environmental Chemical Engineering, 2026)

Human aldo-keto reductases (AKR1C1-AKR1C3) increase the mutagenicity of environmental nitroarenes in the mammalian HPRT forward gene mutagenicity assay - Anthony L. Su; Cátia F. Marques; Karam El-Bayoumy; Trevor M. Penning (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

On the importance of soil texture for predicting future global soil respiration - Lucas Carvalho Gomes; Cássio Marques Moquedace; Ivan F. Souza; Ben Bond-Lamberty; Rodrigo Vargas; Lars Vesterdal; Gustavo V. Veloso; Marcio Rocha Francelino; Carlos E.G.R. Schaefer; Kendalynn A. Morris; Elpídio I. Fernandes-Filho (Science of The Total Environment, 2026)

Bisphenols removal from wastewater in a MBBR-photocatalysis system: Performance and biofilm community dynamics - Amanda F. do Amaral; Marina M.G. Pastre; Rodrigo Coutinho; Lia Teixeira; Marcia Marques (Journal of Water Process Engineering, 2026)

Spatiotemporal groundwater recharge assessment under prolonged drought conditions in São Paulo State, Brazil - Carranco Israel; Hirata Ricardo; Marques Carlos; Conicelli Bruno; Goodarzi Leila; Rörig Fernando; F. Boico Vinicius; Procel Sandra; Hirata Isabela (Sustainable Water Resources Management, 2026)
Following recent prolonged regional droughts, reliance on groundwater resources in São Paulo State, Brazil, has increased, emphasizing the need for robust evaluations of groundwater availability to support integrated water resources management. For this purpose, dependable methods for estimating groundwater recharge were applied. This paper focuses on one of the region’s most important aquifers, the Bauru Aquifer System (BAS), which spans roughly 42% of São Paulo State (≈ 117,000 km²). This paper assesses the spatial and temporal variability of recharge estimates in the BAS using four methods: RISE, RISE corrected, Total Master Recession Curve (MRC), and Annual MRC, based on data from 43 monitoring wells collected between 2009 and 2025. The estimated mean annual groundwater recharge was 147 mm (RISE), 205 mm (RISE corrected), 221 mm (TotalMRC), and 274 mm (Annual MRC), representing approximately 16% to 27% of annual precipitation. Methods that derive a master recession curve from longer time series tend to reduce bias by including a larger number of recession events, thereby decreasing the influence of locally sharp water level drops. Cross-correlation analyses between precipitation and groundwater levels showed that 75% of the wells exhibited the maximum positive correlation at a lag of 70–150 days (2.5–5 months), indicating a slow, delayed response of the aquifer to rainfall. These findings offer valuable insights into recharge quantification and groundwater response times to precipitation in the BAS.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Trends in nematocyst abundance provide a mechanism for venom metering in the ‘upside-down’ jellyfish Cassiopea (Cnidaria: Scyphozoa: Rhizostomeae) - Ranko Gacesa; Adrian Jaimes-Becerra; Edgar Gamero-Mora; Steven Lynham; Gabriel Padilla; André C. Morandini; Antonio C. Marques; Paul F. Long (Journal of Experimental Marine Biology and Ecology, 2026)

Removal of Bisphenol A, Bisphenol S, and Estrogenic Activity from Real Wastewater Using a Multi-stage IFAS System - Amanda F. do Amaral; Alexandre S. A. da Silva; Deivisson L. Cunha; Priscila M. de O. M. Cunha; Rodrigo Coutinho; Marcia Marques (Bulletin of Environmental Contamination and Toxicology, 2026)
This study evaluated the removal of bisphenol A (BPA), bisphenol S (BPS), and estrogenic activity from real municipal wastewater using a pilot-scale multi-stage integrated fixed-film activated sludge (MS-IFAS) system. The configuration comprised five sequential reactors (Anaerobic, Anoxic-1, Aerobic under IFAS, Anoxic-2, and Re-aeration) providing distinct redox conditions. Influent concentrations averaged 112.6 ± 49.5 µg L −1 for BPA and 6.6 ± 3.0 µg L −1 for BPS. Overall removal efficiencies reached 99.8 ± 0.1% and 97.7 ± 1.0%, respectively, despite influent variability. The aerobic IFAS reactor was the main contributor to contaminant degradation, maintaining performance even after a > 90% biomass loss. Estrogenicity, assessed by the Yeast Estrogen Screen assay and expressed as 17β-estradiol equivalents (E2-EQ) decreased by 83.2% (0.031–0.005 ng L −1 ). Effluent E2-EQ values were below ecotoxicological thresholds, indicating negligible estrogenic risk to aquatic organisms. These highlight the strong potential of MS-IFAS for removal of xenoestrogenic contaminants in real wastewater.

Comparative evaluation of otological examination techniques in captive Leopardus guttulus - Maria C.A. Martini; Ana L.R. Marques; Marina Marangoni; Gabrielle C. Freitas; Gentil F. Golçalves; Zalmir S. Cubas; Wanderlei de Moraes; Fabíola Dalmolin; Tatiana Champion (Research in Veterinary Science, 2026)

Sedimentary facies and invertebrate faunal exchange confirm humid conditions in the tropical eastern Atlantic during interglacial Marine Isotopic Stage (MIS) 11c - Carlos S. Melo; José Madeira; Ricardo S. Ramalho; Ana C. Rebelo; Michael W. Rasser; Esther Martín-González; Alfred Uchman; Carlos Marques da Silva; Emílio Rolán; Luís Silva; Joseph A. Stewart; Laura F. Robinson; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Evaluation of global research on agricultural nitrogen pollution between 1990 and 2023: Challenges for more efficacy and equity - J. Serra; J. Marinheiro; C.S.C. Marques-dos-Santos; M. Graversgaard; M. Quemada; L. Lassaletta; G.H. Ros; F. Giannini-Kurina; W. de Vries; E. Aguilera; H.J.M. van Grinsven; K. Hayashi; et al. (Environmental Science & Policy, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Continental influences on post-Marinoan (∼635 Ma) seawater: Chemostratigraphic evidence from the Puga cap carbonate, Amazon Craton margin - Renan F. dos Santos; Afonso C.R. Nogueira; Peter W. Crockford; Davi F. de Carvalho; Juliana C. Marques; Egberto Pereira; Lucieth C. Viera; Pierre Sansjofre; Fábio S. Pereira; Ricardo I.F. Trindade (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A band domain method for controlling numerical simulations of URM structures across modeling approaches - F. Parisse; S. Cattari; R. Marques; P.B. Lourenço (Engineering Structures, 2026)

Multifunctional N,S-doped biochar decorated with transition metals as electrocatalysts for energy conversion applications - Renata Matos; Inês S. Marques; António J.S. Fernandes; Andreia F. Peixoto; Diana M. Fernandes (Biomass and Bioenergy, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Influence of tectonic regime superposition on damage zone structures in a basin-boundary fault, Jatobá basin, NE Brazil - D.L. Vasconcelos; F. Balsamo; L.C. Palhano; F.C.C. Nogueira; F.H.R. Bezerra; F.O. Marques; R.G. Oliveira; W.E. Medeiros; R.A. Fuck; A.C. Tavares; R.R.S. Dantas (Journal of Structural Geology, 2025)

Genomic Signatures of Island Colonisation in Highly Diverse Primates - I. Colmonero‐Costeira; K. Guschanski; S. L. Djaló; N. Fernandes; T. Camará; K. K.‐H. Farh; L. F. K. Kuderna; J. Rogers; T. Marques‐Bonet; M. W. Bruford; I. M. Russo; A. Jensen; et al. (Molecular Ecology, 2025)
Understanding how small populations cope with loss of genetic diversity and deleterious variation is crucial to address the current biodiversity crisis. Insular populations are particularly interesting as they have often persisted at lower population sizes and higher inbreeding than their mainland counterparts. While the genome‐wide consequences of inbreeding in threatened insular species have received some attention, comparative genomics between insular and mainland populations of widespread and genetically diverse species have rarely been performed. Yet, they are particularly well suited to inform about the consequences of drastic population declines from initially large populations—a phenomenon that is becoming increasingly common. The spot‐nosed monkey ( Cercopithecus petaurista ), the Campbell's monkey ( Cercopithecus campbelli ) and the green monkey ( Chlorocebus sabaeus ) are common and genetically diverse West African primates. Insular populations can be found at the Bijagós Archipelago, Guinea‐Bissau. Here, we assessed the genome‐wide diversity, inbreeding, genetic load and adaptive variation using whole genome sequencing data from insular and mainland populations. In the three species, island populations showed lower genome‐wide diversity and higher inbreeding. Genetic drift has likely promoted the conversion of masked genetic load into realised load without increased purging of deleterious variation. Additionally, we found no evidence for accumulation of deleterious variation, suggesting that these populations are not yet at risk of extinction by genetic factors and may act as reservoirs of extant mainland genetic diversity. We highlight, however, that other anthropogenic factors are threatening these insular primates, and therefore conservation management should target their immediate threats and safeguard against additional loss of diversity.

Towards responsible seafood consumption choices: A review of communication tools on health, environmental, and social dimensions - F. Minnens; C. Cardoso; C. Afonso; A. Marques; J. Diogene; H. De Steur; W. Verbeke; Y. Hung (Trends in Food Science & Technology, 2025)

Electric current based automatic classification and operation of EHDA modes - K.S. Moreira; L.P. Di Bonito; K. Glanzer; A. Carrasco-Munoz; F. Di Natale; J.P.M. Marques; P.A. Gabriel; M.E. Oliveira; L.L.F. Agostinho (Journal of Aerosol Science, 2025)

Resilience of soil fauna to pesticide contamination in areas impacted by mining tailings - Tamires R. dos Reis; Paulo R.L. Alves; Márcio R. Nunes; Felipe O. Bandeira; Letícia C.V. Silva; Artur F. de Souza; Aline O. Silva; Soraya A. Botelho; João J.G.S.M. Marques; Marco A.C. Carneiro (Science of The Total Environment, 2025)

Exploring In Vitro Mesenchymal Stem Cell Osteodifferentiation via Vibrational Microspectroscopy: A Review - Daniela S. Bispo; Inês C. R. Graça; João A. Rodrigues; João T. S. Martins; Mariela M. Nolasco; Maria P. M. Marques; Helena I. S. Nogueira; João F. Mano; Mariana B. Oliveira; Paulo J. A. Ribeiro-Claro; Ana M. Gil (Stem Cell Reviews and Reports, 2025)
The application of vibrational microspectroscopy to the study of in vitro mesenchymal stem cells (MSC) osteogenic differentiation is a promising approach towards the understanding of the molecular processes involved in bone fabrication. Both infrared (IR) and Raman microspectroscopies have been applied, with a clear predominance of the latter. Bone marrow MSC have been the target of most studies, followed by those originating from dental/oral and adipose tissues. Interests have increasingly addressed single cell and extracellular matrix characterization at the molecular level. Most studies have focused on the characteristics and maturity of time-course mineralization, attempting to localize mineral aggregates formed onto the evolving collagen strands. Some reports have focused on time-dependent changes in protein structure and other components of extracellular matrix components. Besides spectral band examination through position, linewidth and shape, selected band ratios have proved largely informative to assess mineral species evolution and mineral-to-organic matrix interactions over time. The increasing use of multivariate analysis (or chemometrics) and machine learning strategies to detect finer spectral variations is evident, as is the promise of more recent IR and Raman variations to provide higher sensitivity and spatial resolution conditions. The label-free non-invasive nature of vibrational microspectroscopy makes it particularly promising for rapid and effective selection of suitable MSC donors, to support scale-up procedures for translation to the clinic. Some of the challenges to be faced are briefly discussed. Graphical Abstract

Impacts of rural and urban sources on a tropical semiarid region (Acaraú River, Ceará, Brazil): sedimentary sterols and endocrine-disrupting compounds as anthropogenic molecular markers - Rivelino M. Cavalcante; Antonio D. S. Pereira; Marcielly F. B. Lima; Pollyana Morais; Elissandra V. Marques; Gabrielle M. Fernandes; Rafael P. Santos; Ronaldo F. Nascimento; Felipe R. Santos; Lucas B. Moreira (Environmental Geochemistry and Health, 2025)

LP-37 Ciprofloxacin alters neuronal epigenetic patterns in vitro and in vivo at therapeutically relevant exposures - F. Panza; S. Marques; E. Panebianco; C. Pereira-Teixeira; V. Stevanović; J. Aranđelović; M. Savić; H. Carmo; S. Sá; F. Carvalho; J.P. Silva (Toxicology Letters, 2025)

P31-19 Rimonabant alters histone modification patterns of neuronal cells at pharmacologically-relevant concentrations - M. Moura; C. Teixeira; S. Marques; F. Panza; F. Carvalho; J.P. Silva (Toxicology Letters, 2025)

Accuracy assessment of PlanetScope SuperDove products for aquatic reflectance retrieval over Brazilian inland and coastal waters - Rafael G. Chasles; Daniel A. Maciel; Claudio C.F. Barbosa; Evlyn M.L.M Novo; Vitor S. Martins; Rejane Paulino; Raianny Wanderley; Rogério F. Júnior; Thainara M. Lima; Pedro Bacellar; Julio C.P. dos Santos; Ana Clara da C. Silva; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Effect of Soil Compaction Caused by Manual and Mechanized Harvesting Management on Sugarcane Yield - Aldir Carpes Marques Filho; Murilo Battistuzzi Martins; Lucas Santos Santana; Arthur Gabriel Caldas Lopes; Renato Lustosa Sobrinho; Emerson F. C. Souza; Mohammad K. Okla; Ibrahim A. Alaraidh (Sugar Tech, 2025)

Pharmaceuticals, Personal Care Products and Plasticizers in Surface Water and Environmental Risk Assessment: Guandu River Basin, Rio de Janeiro/Brazil - Frederico G. de Araujo; Glauco F. Bauerfeldt; Deivisson L. Cunha; Eduardo M. Martins; Marcia Marques (Water, Air, & Soil Pollution, 2025)

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

Estimation of diurnal and nocturnal radiation balance in tropical ecosystems - D. O. Maionchi; I. J. C. de Paulo; S. R. de Paulo; J. B. Marques; A. L. P. Junior; H. J. A. da Silva; R. S. Palácios; T. R. Rodrigues; T. A. dos Santos; A. M. S. Lima; M. S. Biudes; L. Sanches; et al. (Theoretical and Applied Climatology, 2025)

Macroptilium yellow vein virus (Begomovirus macroptilivenae) associated with Macroptilium plants is geographically structured into divergent subpopulations - Aline Marques Melo; Ayane Fernanda Ferreira Quadros; João Paulo Herrera da Silva; Roberto Ramos-Sobrinho; Mayra Machado de Medeiros Ferro; Sarah Jacqueline Cavalcanti da Silva; Iraildes Pereira Assunção; Gaus Silvestre de Andrade Lima; F. Murilo Zerbini (Archives of Virology, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

A Comprehensive Framework for Water Affordability Analysis - T. S. Fagundes; R. C. Marques; T. F. Malheiros (Water Resources Management, 2025)
Water and sanitation affordability has emerged as a significant concern in recent years due to economic crises and the increasing reliance on tariffs to finance public services. Governments have often depended on inadequate affordability analyses, if any, to identify constraints faced by vulnerable families in accessing water supply and sanitation services. This paper proposes a comprehensive affordability analysis framework, considering six key dimensions: coverage rates, conventional affordability ratio, community poverty conditions, affordability ratio for poorer households, access to water social programs, and the burden of connection fees. The framework was applied to Brazil, focusing on its state-owned providers, which serve more than 70% of the population. The results demonstrate that the proposed framework offers a simple yet robust tool for decision-makers globally, with the flexibility to adapt to various contexts. The case study revealed that the Brazil’s conventional affordability ratio masks affordability issues faced by poorer families, along with low access to social tariffs, high incidence of poverty, and low coverage in several areas. These findings provide critical insights for stakeholders, enabling the development of targeted public policies and the design of appropriate subsidy mechanisms.

In situ volcanically baked killarney fern fossils (Hymenophyllaceae) from the late Holocene of the Azores archipelago (Portugal) - C.A. Góis-Marques; F. Rumsey; J. Madeira; M. Menezes de Sequeira (Review of Palaeobotany and Palynology, 2025)

Sex-specific reproductive impairment in Pacific oysters (Magallana gigas) exposed to TiO2 NPs: A focus on gonadal status - F Fernández-García; A Marques; S Jerónimo; I. B Oliveira; A Carvalhais; V Pereira; J.F Asturiano; M Pacheco; C Mieiro (Marine Environmental Research, 2025)

Analysis of free-living seabirds from Brazil as potential hosts of Toxoplasma gondii and serological investigation for antibodies against Leptospira spp. - Igor C. L. Acosta; Daniela P. Chiebao; Patricia P. Serafini; Gabriel Canani; Hilda F. J. Pena; Marcos B. Heinemann; Antonio F. Souza-Filho; Cynthia Campolina; Caio A. Marques; Tatiana S. Neves; Marcio A. Efe; Guilherme T. Nunes; et al. (Veterinary Research Communications, 2025)

Landscape influences bat suppression of pine processionary moth: Implications for pest management - A.M. Augusto; S. Pereira; S. Rodrigues; F. Marques; O. Aizpurua; A. Alberdi; G. Jones; O. Razgour; T.A. Marques; D. Russo; H. Rebelo (Journal of Environmental Management, 2025)

Identifying changes in the drivers of ecosystem services: Socioeconomic changes underlie reduced provision of pollination service - Pedro Joaquim Bergamo; Kátia F. Rito; Kayna Agostini; Felipe Deodato da Silva e Silva; Márcia M. Maués; André R. Rech; Lucas A. Garibaldi; Eimear Nic Lughadha; Antonio M. Saraiva; Rodrigo Y. Tsukahara; Blandina F. Viana; Grasiela Casas; et al. (Journal of Environmental Management, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Bioprocess to produce biostimulants/biofertilizers based on microalgae grown using piggery wastewater as nutrient source - Alice Ferreira; Diego O. Corrêa; Belina Ribeiro; Teresa Lopes da Silva; Cláudia Marques-dos-Santos; F. Gabriel Acién; Luisa Gouveia (Bioresource Technology, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Thermal performance of native and invasive crab species: investigating the invasion potential of Hemigrapsus takanoi in southern European Carcinus maenas’ habitats - L. D. Rato; T. Simões; S. C. Novais; J. M. Damasceno; J. Van der Meer; D. W. Thieltges; J. C. Marques; M. F. L. Lemos (Biological Invasions, 2024)
Invasive species’ plasticity and latitudinal spread have become an increasing matter of concern in rapidly changing climate. The brush-clawed shore crab ( Hemigrapsus takanoi ), native along northwestern Pacific shores, has established dense populations in northern European coasts. Detrimental effects in natura have been reported, such as displacement of native species and competition for shelter, rasing concerns regarding shellfish early life stages and food webs-posing a threat to wild stocks’ recruitment and aquaculture. The species has not yet been observed in southern European countries (e.g., Portugal), where niche habitats such as harbours, mudflats, and lagoons reach higher temperatures than the invaded northern range. The aims of this study were to determine H. takanoi potential to acclimate to a southern thermal range, assess thermal performance, and identify potential competitive advantages over the native shore crab Carcinus maenas . This was accomplished through individual exposure to one of three treatments, resembling a southern European thermal range (17 °C, 21 °C, or 25 °C), for 30 days. H. takanoi thrived in temperatures as high as 25 °C, a realistic thermal scenario in Óbidos Lagoon (the biggest Portuguese lagoon)—while the native shore crab C. maenas underperformed at that treatment, showing lower survival, growth, and feed intake than H. takanoi . These results suggest that H. takanoi may be able to colonise southern and warmer European locations and have higher plasticity than the native species already inhabiting areas close to its upper thermal limits. Under global warming scenarios, inferences of further latitudinal spread and increased invaded range may also be taken to the invaded northern European habitats.

A Tropical Estuary Where Mercury Does Not Biomagnify and its Adjacent Waters that Render Extremely High Mercury Concentrations in Top Predators - Paulo R. Dorneles; Thaís de C. Paiva; Gabriel P. Bighetti; Dhoone Menezes; António M. B. Marques; Patricia S. L. Anacleto; Leonardo Flach; Fabíola H. S. Fogaça; Ana Paula C. Farro; Mariana F. Nery; Ana Lúcia Cypriano-Souza; Mirela D’arc; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Effects of anticoagulants time storage on stable isotope values of crocodilians’ blood tissues - Luciana M. Beloto; Neliton R. F. Lara; Luís A. B. Bassetti; Beatriz F. Littig; Ronnie V. M. Ferreira; Luciano M. Verdade; Plínio B. Camargo; Thiago S. Marques (Isotopes in Environmental and Health Studies, 2024)

P07-11 Ciprofloxacin alters synaptic and immune proteins in rat brain areas linked to emotional, reward, and cognitive functions - S.I. Marques; E. Panebianco; V. Stevanovic; J. Arandelovic; M. Savic; H. Carmo; F. Carvalho; S.I. Sá; J.P. Silva (Toxicology Letters, 2024)

P06-04 Advancing bladder cancer detection: unveiling a novel urinary biomarker panel through metabolomics - Â. Carapito; A. Teixeira-Marques; C. Jerónimo; R. Henrique; A.C.A. Roque; F. Carvalho; J. Pinto; P. Guedes de Pinho (Toxicology Letters, 2024)

Endopolyploidy and its role in shaping ant castes and colony dynamics: a study on Camponotus aff. balzani (Hymenoptera, Formicidae) - M. G. Tavares; J. E. Serrão; L. L. Bhering; A. C. Marques; F. A. F. Soares; W. R. Clarindo (Insectes Sociaux, 2024)

Shake-table testing of a stone masonry building aggregate: overview of blind prediction study - I. Tomić; A. Penna; M. DeJong; C. Butenweg; A. A. Correia; P. X. Candeias; I. Senaldi; G. Guerrini; D. Malomo; B. Wilding; D. Pettinga; M. Spanenburg; et al. (Bulletin of Earthquake Engineering, 2024)
City centres of Europe are often composed of unreinforced masonry structural aggregates, whose seismic response is challenging to predict. To advance the state of the art on the seismic response of these aggregates, the Adjacent Interacting Masonry Structures (AIMS) subproject from Horizon 2020 project Seismology and Earthquake Engineering Research Infrastructure Alliance for Europe (SERA) provides shake-table test data of a two-unit, double-leaf stone masonry aggregate subjected to two horizontal components of dynamic excitation. A blind prediction was organized with participants from academia and industry to test modelling approaches and assumptions and to learn about the extent of uncertainty in modelling for such masonry aggregates. The participants were provided with the full set of material and geometrical data, construction details and original seismic input and asked to predict prior to the test the expected seismic response in terms of damage mechanisms, base-shear forces, and roof displacements. The modelling approaches used differ significantly in the level of detail and the modelling assumptions. This paper provides an overview of the adopted modelling approaches and their subsequent predictions. It further discusses the range of assumptions made when modelling masonry walls, floors and connections, and aims at discovering how the common solutions regarding modelling masonry in general, and masonry aggregates in particular, affect the results. The results are evaluated both in terms of damage mechanisms, base shear forces, displacements and interface openings in both directions, and then compared with the experimental results. The modelling approaches featuring Discrete Element Method (DEM) led to the best predictions in terms of displacements, while a submission using rigid block limit analysis led to the best prediction in terms of damage mechanisms. Large coefficients of variation of predicted displacements and general underestimation of displacements in comparison with experimental results, except for DEM models, highlight the need for further consensus building on suitable modelling assumptions for such masonry aggregates.

A multi-tier methodology for the estimation of individual-specific parameters of DEB models - Diogo F. Oliveira; Gonçalo M. Marques; Nuno Carolino; José Pais; João M.C. Sousa; Tiago Domingos (Ecological Modelling, 2024)

A biofloc system avoids the adverse effects of diets with suboptimal protein levels on zootechnical performance, intestinal histomorphometry, and protein metabolism of Nile tilapia juvenile fed Spirulina biomass (Arthrospira platensis) as an alternative protein source - Fernanda Picoli; Alana D. de Oliveira; Suelyn O. Marques; Deise C. Terhorst; Suélen Serafini; Luísa Nora; Fabio F. Neves; Maurício G. C. Emerenciano; Diogo L. A. Lopes; Aleksandro S. da Silva; Thiago E. H. P. Fabregat (Fish Physiology and Biochemistry, 2024)

Beta diversity and regionalization of the western Atlantic marine biota - Ubirajara Oliveira; Fernanda Azevedo; Alan Dias; Ana Carolina Sousa de Almeida; André R. Senna; Antonio C. Marques; Dafinny Rezende; Eduardo Hajdu; Erick Alves Pereira Lopes‐Filho; Fábio Bettini Pitombo; Gabriela Moura de Oliveira; João Gabriel Doria; et al. (Journal of Biogeography, 2024)
Aim Understanding the factors determining marine community variations is important for biogeography and conservation. Beta diversity is a metric for mapping species composition variations between communities and regionalizing biota. Ecoregions are commonly used for regionalization, but their empirical testing has been limited. Our aim is to map marine species composition variations in the Western Atlantic, identify variables related to these variations, and regionalize areas based on community distribution. Additionally, we test whether currently proposed ecoregions represent unique biota units and specific environmental conditions. Location Western Atlantic Ocean. Taxon Vertebrates, invertebrates and algae. Methods We constructed a large marine biodiversity database, including vertebrates, invertebrates, and algae, totalling over 4 million records. We used the generalized dissimilarity model (GDM) to identify variables most related to species composition variations and map beta‐diversity variations. We employed an unsupervised classifier for community regionalization. To test if the ecoregion regionalization boundaries are corroborated by species distribution data, we used the Sørensen index. To assess if ecoregions correspond to environmental units, we checked if areas had distinct environmental conditions using a PCA of 134 marine environmental variables. Results The GDM explained a high variation in species composition, 61% in the complete database. Analysing vertebrates, invertebrates and algae separately also yielded relatively high results: 46%, 54%, and 33%, respectively. Coastal areas differed from open sea areas in composition. Environmental variables combined better explained beta diversity than isolated variables. The regionalization based on GDM was not congruent with ecoregion boundaries. Moreover, ecoregions showed no distinction in species composition or environmental conditions. Main Conclusions This study's regionalization is crucial for marine biodiversity conservation, focusing on understanding species composition patterns between coastal and open sea areas to develop tailored conservation strategies. Despite sampling limitations, the study advances marine biogeography knowledge by analysing over 4 million species records and 134 environmental variables. This comprehensive approach enhances understanding marine species distribution and diversity and aiding the development of effective conservation measures.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Assessing nitrate groundwater hotspots in Europe reveals an inadequate designation of Nitrate Vulnerable Zones - J. Serra; C. Marques-dos-Santos; J. Marinheiro; S. Cruz; M.R. Cameira; W. de Vries; T. Dalgaard; N.J. Hutchings; M. Graversgaard; F. Giannini-Kurina; L. Lassaletta; A. Sanz-Cobeña; et al. (Chemosphere, 2024)

Assessing the euryhaline characteristics and metabolic responses of meagre (Argyrosomus regius) when reared under different salinities: Opportunities for aquaculture refinement - Marco F.L. Lemos; Cátia S.E. Silva; Lénia D. Rato; Alexandre F.S. Marques; Ricardo Passos; Irina A. Duarte; Bernardo Duarte; Vanessa F. Fonseca; Sara C. Novais (Aquaculture, 2024)

Emerging and legacy contaminants on the Brazilian southern coast (Santa Catarina): A multi-biomarker approach in oysters Crassostrea gasar (Adanson, 1757) - Camila L.V. Bastolla; Fernando C. Guerreiro; Miguel Saldaña-Serrano; Carlos H.A.M. Gomes; Daína Lima; Camila F. Rutkoski; Jacó J. Mattos; Vera Helena V. Dias; Bárbara P.H. Righetti; Clarissa P. Ferreira; Julia Martim; Thiago C. Alves; et al. (Science of The Total Environment, 2024)

Systematic review and meta-analysis of randomized controlled trials on the effects of exercise interventions on amyloid beta levels in humans - Isabela Mayer Pucci; Andreo F. Aguiar; Rodrigo M. Pucci; Juliano Casonatto; Sergio Marques Borghi (Experimental Brain Research, 2024)

Antimicrobial prophylaxis in companion animal surgery: A scoping review for European Network for Optimization of Antimicrobial Therapy (ENOVAT) guidelines - T.M. Sørensen; K. Scahill; J. Espinel Ruperez; M. Olejnik; F. Swinbourne; D.R. Verwilghen; M.C. Nolff; S. Baines; C. Marques; A. Vilen; E.L. Duarte; M. Dias; et al. (The Veterinary Journal, 2024)

Effects of the pyriproxyfen and fenthion on the gonadal morphology of Nile tilapia ( Oreochromis niloticus : Perciformes , Cichlidae ) - Glaucia Moises Marques e Silva; Jorge Eduardo Lins Oliveira; Naisandra B. Silva Farias; Raimundo F. A. Júnior; Wallace S. Nascimento (Journal of Fish Biology, 2024)
Commercially available insecticides present acute toxicity to the health of fish and other aquatic organisms, which may impair the local aquaculture. This study evaluated the gonadal morphology of freshwater fish exposed to pyriproxyfen and fenthion. Forty‐five juvenile male Nile tilapias ( Oreochromis niloticus ) were divided into control, pyriproxyfen‐exposed (0.01 g/L), and fenthion‐exposed (0.001 g/L) groups. They were evaluated in three moments (30, 60, and 90 days). The variables analyzed were the gonadosomatic index (GSI), weight to length ratio, seminiferous tubules morphometry (diameter and height), tissue damage, and immunohistochemical analysis for caspase‐3, tumor necrosis factor alpha (TNF‐α), and vascular endothelial growth factor (VEGF). Pyriproxyfen and fenthion injured the seminiferous tubule tissue, and the damage progressed according to the exposure time. In addition, the GSI gradually reduced over time in all groups compared with the first moment (30 days), while caspase‐3, TNF‐α, and VEGF values increased only in the fenthion‐exposed group. Therefore, pyriproxyfen and fenthion changed the gonadal morphology of male Oreochromis niloticus , which may affect their reproduction in the wild or captivity.

How can landscape visual assessment inform landscape planning and management? – Alto Douro Wine region case study, Portugal - Ana Medeiros; Cláudia Fernandes; João F. Gonçalves; Paulo Farinha-Marques; Isabel Martinho Da Silva (Applied Geography, 2024)

Effect of biomass burning emission on carbon assimilation over Brazilian Pantanal - Leone F. A. Curado; Sérgio R. de Paulo; Haline J. Araújo da Silva; Rafael S. Palácios; João B. Marques; Iramaia Jorge Cabral de Paulo; Higo José Dalmagro; Thiago Rangel Rodrigues (Theoretical and Applied Climatology, 2024)

Systematization of spatial functional layouts and pedestrian wind comfort assessment for an ultra-thin triangular free form shell structure - J.H. Sousa; M. Glória Gomes; F. Marques da Silva; A. Tomé (Building and Environment, 2023)

Hierarchical structure of 3D ZnO experimentally designed to achieve high performance in the sertraline photocatalysis in natural waters - Thalles E.M. Silva; Ailton J. Moreira; Eryka T.D. Nobrega; Ridien G. Alencar; Pietra T. Rabello; Sirlon F. Blaskievicz; Gleison N. Marques; Lucia H. Mascaro; Elaine C. Paris; Sherlan G. Lemos; Ernesto C. Pereira; Gian P.G. Freschi (Chemical Engineering Journal, 2023)

Stromal cell-derived factor 1 (SDF-1) increases the number of telocytes in ex vivo and in vitro assays - Bruno Domingos Azevedo Sanches; Guilherme Henrique Tamarindo; Alana Della Torre da Silva; Gustavo Matheus Amaro; Juliana dos Santos Maldarine; Vitória Alário dos Santos; Luiz Henrique Alves Guerra; Carolina Marques Bedolo Baraldi; Rejane Maira Góes; Sebastião Roberto Taboga; Hernandes F. Carvalho (Histochemistry and Cell Biology, 2023)

Permission to pass: on the role of p53 as a gatekeeper for aneuploidy - Joana F. Marques; Geert J. P. L. Kops (Chromosome Research, 2023)
Aneuploidy—the karyotype state in which the number of chromosomes deviates from a multiple of the haploid chromosome set—is common in cancer, where it is thought to facilitate tumor initiation and progression. However, it is poorly tolerated in healthy cells: during development and tissue homeostasis, aneuploid cells are efficiently cleared from the population. It is still largely unknown how cancer cells become, and adapt to being, aneuploid. P53, the gatekeeper of the genome, has been proposed to guard against aneuploidy. Aneuploidy in cancer genomes strongly correlates with mutations in TP53 , and p53 is thought to prevent the propagation of aneuploid cells. Whether p53 also participates in preventing the mistakes in cell division that lead to aneuploidy is still under debate. In this review, we summarize the current understanding of the role of p53 in protecting cells from aneuploidy, and we explore the consequences of functional p53 loss for the propagation of aneuploidy in cancer.

A giant volcanic island in an early Martian Ocean? - A. Hildenbrand; H. Zeyen; F. Schmidt; S. Bouley; F. Costard; P.Y. Gillot; F.O. Marques; X. Quidelleur (Earth and Planetary Science Letters, 2023)

OS03-01: Astrocyte response in rat brain is affected by pharmacologically-relevant doses of pharmaceuticals associated with neuropsychiatric/psychological adverse events - S.I. Marques; V. Stevanović; J. Aranđelović; M. Savić; H. Carmo; F. Carvalho; S.I. Sá; J.P. Silva (Toxicology Letters, 2023)

One-year variation in quantity and properties of microplastics in mussels (Mytilus galloprovincialis) and cockles (Cerastoderma edule) from Aveiro lagoon - M.J. Botelho; C. Vale; F. Marques; C. Moreirinha; S.T. Costa; L. Guilhermino; S. Joaquim; D. Matias; M. Candeias; A. Rudnitskaya (Environmental Pollution, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Impact of extreme wildfires from the Brazilian Forests and sugarcane burning on the air quality of the biggest megacity on South America - Carlos E. Souto-Oliveira; Márcia T.A. Marques; Thiago Nogueira; Fabio J.S. Lopes; José A.G. Medeiros; Ilca M.M.A. Medeiros; Gregori A. Moreira; Pedro Leite da Silva Dias; Eduardo Landulfo; Maria de F. Andrade (Science of The Total Environment, 2023)

Silver nanoparticles and silver ions indistinguishably decrease sperm motility in Pacific oysters (Magallana gigas) after short-term direct exposure - Fátima Fernández-García; Ana Carvalhais; Ana Marques; Isabel B. Oliveira; Sofia Guilherme; Helena Oliveira; Catarina C.V. Oliveira; Elsa Cabrita; Juan F. Asturiano; Mário Pacheco; Cláudia Mieiro (Environmental Toxicology and Pharmacology, 2023)

The distribution of coastal fish eDNA sequences in the Anthropocene - Laetitia Mathon; Virginie Marques; Stéphanie Manel; Camille Albouy; Marco Andrello; Emilie Boulanger; Julie Deter; Régis Hocdé; Fabien Leprieur; Tom B. Letessier; Nicolas Loiseau; Eva Maire; et al. (Global Ecology and Biogeography, 2023)
Aim Coastal fishes have a fundamental role in marine ecosystem functioning and contributions to people, but face increasing threats due to climate change, habitat degradation and overexploitation. The extent to which human pressures are impacting coastal fish biodiversity in comparison with geographic and environmental factors at large spatial scale is still under scrutiny. Here, we took advantage of environmental DNA (eDNA) metabarcoding to investigate the relationship between fish biodiversity, including taxonomic and genetic components, and environmental but also socio‐economic factors. Location Tropical, temperate and polar coastal areas. Time period Present day. Major taxa studied Marine fishes. Methods We analysed fish eDNA in 263 stations (samples) in 68 sites distributed across polar, temperate and tropical regions. We modelled the effect of environmental, geographic and socio‐economic factors on α‐ and β‐diversity. We then computed the partial effect of each factor on several fish biodiversity components using taxonomic molecular units (MOTU) and genetic sequences. We also investigated the relationship between fish genetic α‐ and β‐diversity measured from our barcodes, and phylogenetic but also functional diversity. Results We show that fish eDNA MOTU and sequence α‐ and β‐diversity have the strongest correlation with environmental factors on coastal ecosystems worldwide. However, our models also reveal a negative correlation between biodiversity and human dependence on marine ecosystems. In areas with high dependence, diversity of all fish, cryptobenthic fish and large fish MOTUs declined steeply. Finally, we show that a sequence diversity index, accounting for genetic distance between pairs of MOTUs, within and between communities, is a reliable proxy of phylogenetic and functional diversity. Main conclusions Together, our results demonstrate that short eDNA sequences can be used to assess climate and direct human impacts on marine biodiversity at large scale in the Anthropocene and can further be extended to investigate biodiversity in its phylogenetic and functional dimensions.

Review of tectonic inversion of sedimentary basins in NE and N Brazil: Analysis of mechanisms, timing and effects on structures and relief - Francisco H. Bezerra; Fernando O. Marques; David L. Vasconcelos; Dilce F. Rossetti; Aline C. Tavares; Rubson P. Maia; David L. de Castro; Francisco C.C. Nogueira; Reinhardt A. Fuck; Walter E. Medeiros (Journal of South American Earth Sciences, 2023)

Can N2 fixation by forage legumes build soil organic matter to rival fertilizer N in a tropical forest biome? - Wesley dos Santos Souza; Claudia de Paula Rezende; José Marques Pereira; Rafael Cassador Monteiro; Camila A. dos Santos; Robert de Oliveira Macedo; Fabiano Barbosa Alecrim; Érika F. Machado Pinheiro; David V.B. de Campos; Segundo Urquiaga; Bruno J.R. Alves; Robert M. Boddey (Geoderma Regional, 2023)

Synthesis and characterization of adsorbent materials for the retention of elemental mercury from contaminated tropical soils - J. R. Oliveira; I. C. F. Vasques; F. R. D. Lima; M. T. P. Job; G. S. Carvalho; T. S. Oliveira; J. J. Marques (International Journal of Environmental Science and Technology, 2023)

Spatiotemporal Distribution Patterns of the Sea Cucumber Holothuria arguinensis on a Rocky-Reef Coast (Northeast Atlantic) - F. Azevedo e Silva; A. C. Brito; A. Pombo; T. Simões; T. A. Marques; C. Rocha; A. S. Madruga; J. Sousa; E. Venâncio; P. M. Félix (Estuaries and Coasts, 2023)
The demand for sea cucumbers from the NE-Atlantic is increasing as a consequence of the depletion of stocks that historically supplied Asian markets. Some species from the NE-Atlantic are already showing overfishing signs due to either inefficient policies or their total absence, and they do not offer any margins of sustainability to sea cucumber fisheries. The current lack of knowledge of biological and ecological traits has led to ineffective protection of those species. Holothuria arguinensis is a good example of a temperate sea cucumber species suffering from the effects of unregulated and illegal harvest. This study aims to determine the temporal and spatial distribution patterns of H. arguinensis , assessing density and size-class structure in a NE-Atlantic population, in SW Portugal, as a function of environmental conditions. Sampling was done every 1.5 months at 6 stations defined according to habitat heterogeneity, following the coastline from the mouth of the Sado estuary to marine coastal areas. At each station, there were two habitats (rocky substrate and sandy areas) sampled through SCUBA diving along 30-m random transects, each with three replicates. Individuals were counted and measured (total length) and individual behavioural parameters, such as sheltering and settlement surface, were recorded. Water column parameters, sediment composition, and substrate cover were also recorded. Generalised Linear Models were fit to the data, modelling density and size distribution of the species with respect to environmental conditions. The results indicate that the distribution of H. arguinensis was mainly determined by its ability to deal with physical environmental stressors (current), rather than the chemical properties of the water column or sediment composition. The hydrodynamic features of the region exert the greatest impact on this species’ distribution and help shape habitat usage by different size class groups.

New, fast, and precise method of COVID-19 detection in nasopharyngeal and tracheal aspirate samples combining optical spectroscopy and machine learning - Denny M. Ceccon; Paulo Henrique R. Amaral; Lídia M. Andrade; Maria I. N. da Silva; Luis A. F. Andrade; Thais F. S. Moraes; Flavia F. Bagno; Raissa P. Rocha; Daisymara Priscila de Almeida Marques; Geovane Marques Ferreira; Alice Aparecida Lourenço; Ágata Lopes Ribeiro; et al. (Brazilian Journal of Microbiology, 2023)

From piggery wastewater to wheat using microalgae towards zero waste - Alice Ferreira; Daniel Figueiredo; Francisca Ferreira; Ana Marujo; Carolina R.V. Bastos; Guillermo Martin-Atanes; Belina Ribeiro; Karolína Štěrbová; Cláudia Marques-dos-Santos; F. Gabriel Acién; Luisa Gouveia (Algal Research, 2023)

Impacts of Covid-19 interventions on air quality: evidence from Brazilian metropolitan regions - F. C. Silva; D. H. Silva; K. M. Zamprogna; S. S. Souza; D. Sell; J. Sabatini-Marques; T. Yigitcanlar (International Journal of Environmental Science and Technology, 2023)
The Covid-19 pandemic has negatively disrupted the way our economy and society functions. Nonetheless, there have also been some positive externalities of the pandemic on the environment. This paper aims to evaluate the concentration of nitrogen dioxide in Brazilian metropolitan regions after the policies adopted to confront Covid-19. In terms of methodological approach, the study employs cross-sectional quantitative analyses to compare the period of 36 days, i.e., 12 March to 16 April—before (in 2019) and after (in 2020) the pandemic declaration. The data were obtained from the Sentinel 5-P low-Earth polar satellite concerning Brazilian metropolitan regions ( n = 24). Thorough spatial and statistical analyses were undertaken to identify the pre- and during pandemic nitrogen dioxide concentrations. Complementarily, Spearman’s correlation test was performed with variables that impact air quality. The study results a fall in nitrogen dioxide concentration levels in 21 of the 24 metropolitan regions which was observed. The Spearman’s correlation coefficient between the nitrogen dioxide variation and the vehicle density was 0.485, at a significance level of 0.05. With these findings in mind, the paper advocates that while the pandemic has a significant negative consequence on the health of population globally, a series of measures that result in a new social organization directly interfere in the reduction of air pollution that contributes to the quality of the air we breathe.

Differentiation and Maturation of Muscle and Fat Cells in Cultivated Seafood: Lessons from Developmental Biology - Claire Bomkamp; Lisa Musgrove; Diana M. C. Marques; Gonçalo F. Fernando; Frederico C. Ferreira; Elizabeth A. Specht (Marine Biotechnology, 2023)
Cultivated meat, also known as cultured or cell-based meat, is meat produced directly from cultured animal cells rather than from a whole animal. Cultivated meat and seafood have been proposed as a means of mitigating the substantial harms associated with current production methods, including damage to the environment, antibiotic resistance, food security challenges, poor animal welfare, and—in the case of seafood—overfishing and ecological damage associated with fishing and aquaculture. Because biomedical tissue engineering research, from which cultivated meat draws a great deal of inspiration, has thus far been conducted almost exclusively in mammals, cultivated seafood suffers from a lack of established protocols for producing complex tissues in vitro. At the same time, fish such as the zebrafish Danio rerio have been widely used as model organisms in developmental biology. Therefore, many of the mechanisms and signaling pathways involved in the formation of muscle, fat, and other relevant tissue are relatively well understood for this species. The same processes are understood to a lesser degree in aquatic invertebrates. This review discusses the differentiation and maturation of meat-relevant cell types in aquatic species and makes recommendations for future research aimed at recapitulating these processes to produce cultivated fish and shellfish.

Hybridization and genetic characterization of sea turtles in Alagoas, northeastern Brazil - João P. F. A. Almeida; Oscar K. L. Marques; Tamí Mott; Robson G. Santos (Marine Biology, 2023)

Cost and environmental impact assessment of mandatory speed reduction of maritime fleets - Crístofer H. Marques; Paula C. Pereda; Andrea Lucchesi; Ramiro F. Ramos; Olav Fiksdahl; Luiz F. Assis; Newton N. Pereira; Jean-David Caprace (Marine Policy, 2023)

Influence of Constant Rate Infusions of Fentanyl Alone or in Combination With Lidocaine and Ketamine on the Response to Surgery and Postoperative Pain in Isoflurane Anesthetized Dogs Undergoing Unilateral Mastectomy: A Randomized Clinical Trial - Éder J. Marques; Eduardo R. Monteiro; José R. Herrera-Becerra; Débora Tomazeli; Inácio B. Rovaris; Tiago F. de Oliveira; Stella de F. Valle; Marcelo M. Alievi (Topics in Companion Animal Medicine, 2023)

Composites of EVA and hydrophobically modified PAMAM dendrimer: Effect of composition on crystallization and flow assurance of waxy systems - Bruna F. Alves; Thiago M. Rossi; Luiz Carlos C. Marques; Bluma G. Soares; Elizabete F. Lucas (Fuel, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Ants of Brazil: an overview based on 50 years of diversity studies - Rodrigo M. Feitosa; Gabriela P. Camacho; Thiago S. R. Silva; Mônica A. Ulysséa; Natalia Ladino; Aline M. Oliveira; Emília Z. Albuquerque; Fernando A. Schmidt; Carla R. Ribas; Anselmo Nogueira; Fabrício B. Baccaro; Antônio C. M. Queiroz; et al. (Systematics and Biodiversity, 2022)

Isolation by distance and past climate resistance shaped the distribution of genealogical lineages of a neotropical lizard - Felipe Camurugi; Eliana F. Oliveira; Guilherme S. Lima; Ricardo Marques; Felipe M. Magalhães; Guarino R. Colli; Daniel O. Mesquita; Adrian A. Garda (Systematics and Biodiversity, 2022)

Potential effects of warming on the trophic structure of shallow lakes in South America: a comparative analysis of subtropical and tropical systems - José Luiz Attayde; Rosemberg F. Menezes; Sarian Kosten; Gissell Lacerot; Erik Jeppesen; Vera Huszar; Christina W. Castelo Branco; David da Mota-Marques; Carla Kruk; Franco Teixeira-de-Mello; José H. C. Gomes; Celia C. C. Machado; et al. (Hydrobiologia, 2022)

Characteristics and mechanisms of multistage dolomitization in Proterozoic dolomitic breccia from Água Clara Formation, Ribeira Belt, Brazil - Murilo Henrique Taques Camargo; André D. Ferreira; Cristina V. Pinto-Coelho; Lucilia A. R. de Oliveira; Marcella L. Cavallari; Lorena de F. Alfaro; Alberto C. Botelho; Júlio T. Brita; Cláudio N. Lamarão; Gisele T. Marques; Eduardo Roemers-Oliveira (Carbonates and Evaporites, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Estimating intrinsic growth rates of arthropods from partial life tables using predatory mites as examples - Arne Janssen; Morgana Maria Fonseca; Italo Marcossi; Milena Oliveira Kalile; Andre Costa Cardoso; Adriana Helena Walerius; Aldo Hanel; Vinicius Marques; Júlia Jantsch Ferla; Vanessa Farias; Paola A. F. Carbajal; Angelo Pallini; et al. (Experimental and Applied Acarology, 2022)
The intrinsic rate of natural increase of a population ( r m ) has been in focus as a key parameter in entomology and acarology. It is considered especially important in studies of predators that are potential biological control agents of fast-growing pests such as mites, whiteflies and thrips. Life-table experiments under controlled laboratory conditions are standard procedures to estimate r m . However, such experiments are often time consuming and may critically depend on the precise assessment of the developmental time and the fecundity rate early in the reproductive phase. Using selected studies of predatory mites with suitable life-table data, we investigated whether and how measurements of growth rates can be simplified. We propose a new method for estimating r m from partial life tables, in which the researcher can choose a level of precision based on a stand-in measure of relative error. Based on this choice, the procedure helps the researcher to decide when a life-table experiment can be terminated. Depending on the chosen precision, significant amounts of experimental time can be saved without seriously compromising the reliability of the estimated growth parameter.

Molecular Detection of Trypanosoma kaiowa in Tabanus triangulum (Diptera: Tabanidae) from the Coastal Plain of Rio Grande do Sul, Southern Brazil - Gratchela D. Rodrigues; Eduardo Blodorn; Ândrio Zafalon-Silva; William Domingues; Roberta Marques; Tiago K. Krolow; Gonzalo Greif; Vinicius F. Campos; Rodrigo F. Krüger (Acta Parasitologica, 2022)

Viability meets suitability: distribution of the extinction risk of an imperiled titi monkey (Callicebus barbarabrownae) under multiple threats - Hamilton Ferreira Barreto; Leandro Jerusalinsky; Anderson A. Eduardo; André Chein Alonso; Eduardo Marques Santos Júnior; Raone Beltrão-Mendes; Stephen F. Ferrari; Sidney F. Gouveia (International Journal of Primatology, 2022)

Ant diversity studies in Brazil: an overview of the myrmecological research in a megadiverse country - F. A. Schmidt; C. R. Ribas; R. M. Feitosa; F. B. Baccaro; A. C. M. de Queiroz; T. G. Sobrinho; Y. Quinet; K. S. Carvalho; T. Izzo; M. S. de Castro Morini; A. Nogueira; H. M. Torezan-Silingardi; et al. (Insectes Sociaux, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Evaluation of Cardiotonic Steroid Modulation of Cellular Cholesterol and Phospholipid - Lilian N. D. Silva; Israel J. P. Garcia; Jessica M. M. Valadares; Marco Tulio C. Pessoa; Marina Marques Toledo; Matheus V. Machado; Mileane Souza Busch; Isabella Rocha; José Augusto F. P. Villar; Georgia C. Atella; Herica L. Santos; Vanessa F. Cortes; et al. (The Journal of Membrane Biology, 2021)

Tumor Tissue Oxidative Stress Changes and Na, K-ATPase Evaluation in Head and Neck Squamous Cell Carcinoma - Marina Marques Toledo; Bruno De Souza Gonçalves; Natalie Mounteer Colodette; Aline Lauda Freitas Chaves; Luciana Vieira Muniz; Rosy Iara Maciel De A. Ribeiro; Hélio Batista Dos Santos; Vanessa F. Cortes; Joao Marcos Arantes Soares; Hérica De Lima Santos; Leandro A. Barbosa (The Journal of Membrane Biology, 2021)

Metabolomic Applications in Stem Cell Research: a Review - Daniela S. C. Bispo; Catarina S. H. Jesus; Inês M. C. Marques; Katarzyna M. Romek; Mariana B. Oliveira; João F. Mano; Ana M. Gil (Stem Cell Reviews and Reports, 2021)

Benzophenone and Diethyl Phthalate Removal from Real Wastewater by a Multi-stage Hybrid Reactor - Amanda F. do Amaral; Alexandre S. A. da Silva; Rodrigo Coutinho; Deivisson L. Cunha; Marcia Marques (Water, Air, & Soil Pollution, 2021)

Irrigation water quality used in paddy-rice fields in the Tejo river basin and its consequences - D. Ferreira; M. Simões; F. Reboredo; F. Pessoa; A. Almeida; M. R. Carvalho; A. Coelho; C. Pessoa; A. Marques; I. Luís; D. Daccak; M. P. Mendes; et al. (Mediterranean Geoscience Reviews, 2021)

Compensatory epistasis explored by molecular dynamics simulations - Catarina Serrano; Carla S. S. Teixeira; David N. Cooper; João Carneiro; Mónica Lopes-Marques; Peter D. Stenson; António Amorim; Maria J. Prata; Sérgio F. Sousa; Luísa Azevedo (Human Genetics, 2021)

Steel mill waste application in soil: dynamics of potentially toxic elements in rice and health risk perspectives - Geila S. Carvalho; Jakeline R. Oliveira; Isabela C. F. Vasques; Monna Lysa T. Santana; Marina Justi; Marcel T. P. Job; Francielle R. D. de Lima; João José Marques (Environmental Science and Pollution Research, 2021)

Curcumin-cinnamaldehyde hybrids as antiproliferative agents against women’s cancer cells - Daiane B. Anselmo; Carlos R. Polaquini; Beatriz C. Marques; Gabriela M. Ayusso; Letícia R. Assis; Guilherme S. Torrezan; Paula Rahal; Ana L. Fachin; Marília F. Calmon; Mozart A. Marins; Luis O. Regasini (Medicinal Chemistry Research, 2021)

Influence of the seasonality and of urban variables in the BTEX and PM2.5 atmospheric levels and risks to human health in a tropical coastal city (Fortaleza, CE, Brazil) - Íthala S. Santiago; Tamiris F. A. Silva; Elissandra V. Marques; Francisco M. de S. Barreto; Antonio G. Ferreira; Camille A. Rocha; Kamila V. Mendonça; Rivelino M. Cavalcante (Environmental Science and Pollution Research, 2021)

Lead acetate ecotoxicity in tropical soils - R. C. S. Alexandrino; F. R. D. Lima; G. C. Martins; T. Natal-da-Luz; J. P. Sousa; L. R. G. Guilherme; J. J. Marques (Ecotoxicology, 2021)

Allometric relationships to assess ontogenetic adaptative changes in three NE Atlantic commercial sea cucumbers (Echinodermata, Holothuroidea) - F. Azevedo e Silva; A. C. Brito; T. Simões; A. Pombo; T. A. Marques; C. Rocha; J. Sousa; E. Venâncio; P. M. Félix (Aquatic Ecology, 2021)

Steel mill waste effects on rice growth: comparison of chemical extractants on lead and zinc availability - Geila S. Carvalho; Jakeline R. Oliveira; Isabela C. F. Vasques; Marina Justi; Monna Lysa T. Santana; Marcel T. P. Job; João José Marques (Environmental Science and Pollution Research, 2021)

Study of physiological and biochemical events leading to vitrification of Arbutus unedo L. cultured in vitro - Mário P. Marques; João Martins; Luís A. E. Batista de Carvalho; Mónica R. Zuzarte; Ricardo M. F. da Costa; Jorge Canhoto (Trees, 2021)

A research perspective towards a more complete biodiversity footprint: a report from the World Biodiversity Forum - Alexandra Marques; Marine Robuchon; Stefanie Hellweg; Tim Newbold; Jutta Beher; Sebastian Bekker; Franz Essl; Daniele Ehrlich; Samantha Hill; Martin Jung; Sandra Marquardt; Francesca Rosa; et al. (The International Journal of Life Cycle Assessment, 2021)

Alterations in functional connectivity are associated with white matter lesions and information processing efficiency in multiple sclerosis - José Miguel Soares; Raquel Conde; Ricardo Magalhães; Paulo Marques; Rosana Magalhães; Luciana Gomes; Óscar F. Gonçalves; Mavilde Arantes; Adriana Sampaio (Brain Imaging and Behavior, 2021)

Toxicity Going Nano: Ionic Versus Engineered Cu Nanoparticles Impacts on the Physiological Fitness of the Model Diatom Phaeodactylum tricornutum - Marco Franzitta; Eduardo Feijão; Maria Teresa Cabrita; Carla Gameiro; Ana Rita Matos; João Carlos Marques; Johannes W. Goessling; Patrick Reis-Santos; Vanessa F. Fonseca; Carlo Pretti; Isabel Caçador; Bernardo Duarte (Frontiers in Marine Science, 2020)
Increasing input of Metal Engineered Nano Particles (MeENPs) in marine ecosystems has raised concerns about their potential toxicity on phytoplankton. Given the lack of knowledge on MeENPs impact on these important primary producers, the effects of Copper Oxide (CuO) ENPs on growth, physiology, pigment profiles, fatty acid (FA) metabolism, and oxidative stress were investigated in the model diatom Pheodactylum tricornutum , to provide suitable biomarkers of CuO ENP exposure versus its ionic counterpart. Diatom growth was inhibited by CuO ENPs but not Ionic Cu, suggesting CuO ENP cytotoxicity. Pulse Modulated Amplitude (PAM) phenotyping evidenced a decrease in the electron transport energy flux, pointing to a reduction in chemical energy generation following CuO ENPs exposure, as well as an increase in the content of the non-functional Cu-substituted chlorophyll a (CuChl a ). A significant decrease in eicosapentaenoic acid (C20:5) associated with a significant rise in thylakoid membranes FAs reflected the activation of counteractive measures to photosynthetic impairment. Significant increase in the omega 6/omega 3 ratio, underline expectable negative repercussions to marine food webs. Increased thiobarbituric acid reactive substances reflected heightened oxidative stress by CuO ENP. Enhanced Glutathione Reductase and Ascorbate Peroxidase activity were also more evident for CuO ENPs than ionic Cu. Overall, observed molecular changes highlighted a battery of possible suitable biomarkers to efficiently determine the harmful effects of CuO ENPs. The results suggest that the occurrence and contamination of these new forms of metal contaminants can impose added stress to the marine diatom community, which could have significant impacts on marine ecosystems, namely through a reduction of the primary productivity, oxygen production and omega 6 production, all essential to sustain heterotrophic marine life.

Evaluation of the Erythrocyte Membrane in Head and Neck Cancer Patients - Bruno De Souza Gonçalves; Marina Marques Toledo; Natalie Mounteer Colodette; Aline Lauda Freitas Chaves; Luciana Vieira Muniz; Rosy Iara Maciel De A. Ribeiro; Hélio Batista Dos Santos; Vanessa F. Cortes; João Marcos Arantes Soares; Leandro A. Barbosa; Hérica de Lima Santos (The Journal of Membrane Biology, 2020)

Molecular characterization of methicillin-resistant and methicillin-sensitive Staphylococcus aureus isolates from human milk samples in Brazil - Jéssica Bomfim de Almeida; Suzi Pacheco de Carvalho; Lucas S. C. da Silva; Yasmin M. F. S. Andrade; Raiane Cardoso Chamon; Kátia Regina Netto dos Santos; Lucas M. Marques (Brazilian Journal of Microbiology, 2020)

Molecular characterization of aureocin 4181: a natural N-formylated aureocin A70 variant with a broad spectrum of activity - Selda Loase Salustiano Marques-Bastos; Marcus Lívio Varella Coelho; Hilana Ceotto-Vigoder; Patrícia Carlin Fagundes; Gabriela Silva Almeida; Dag A. Brede; Ingolf F. Nes; Maria Aparecida Vasconcelos de Paiva Brito; Maria do Carmo de Freire Bastos (Brazilian Journal of Microbiology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bacillus thuringiensis endotoxin production: a systematic review of the past 10 years - José Manoel W. Duarte Neto; Maria Carolina de A. Wanderley; Túlio Alexandre F. da Silva; Daniela A. Viana Marques; Gilvanda R. da Silva; Josimar Fernandes Gurgel; José de Paula Oliveira; Ana Lúcia F. Porto (World Journal of Microbiology and Biotechnology, 2020)

Involvement of adenosine A1 and A2A receptors on guanosine-mediated anti-tremor effects in reserpinized mice - C. M. Massari; L. C. Constantino; N. F. Marques; L. B. Binder; M. Valle-León; M. López-Cano; V. Fernández-Dueñas; F. Ciruela; C. I. Tasca (Purinergic Signalling, 2020)

Nutrient extraction by Helianthus annuus L. irrigated with treated domestic sewage - Daniel da C. Dantas; Enio F. de França e Silva; Renato P. de Lima; Mara S. Marques Dantas; Mario M. Rolim; Gerônimo F. da Silva (Sustainable Water Resources Management, 2020)

Design, synthesis and pharmacological assessment of new pyrazole compounds - Jordana C. Oliveria; Daiany P. B. Silva; Iziara F. Florentino; Lidya C. da Silva; Germán Sanz; Boniek G. Vaz; Francine Pazini; Flávio S. de Carvalho; Luciano M. Lião; Thaís Rosa Marques dos Santos; Marize C. Valadares; Elson A. Costa; et al. (Inflammopharmacology, 2020)

The evolution of Santa Maria Island in the context of the Azores Triple Junction - F. O. Marques; A. Hildenbrand; A. C. G. Costa; A. L. R. Sibrant (Bulletin of Volcanology, 2020)

Toxic effects of lead in plants grown in brazilian soils - Geraldo S. Cândido; Gabriel C. Martins; Isabela C. F. Vasques; Francielle R. D. Lima; Polyana Pereira; Mateus M. Engelhardt; Rayner H. C. L. Reis; João José Marques (Ecotoxicology, 2020)

Deleterious effects of chronic mercury exposure on in vitro LTP, memory process, and oxidative stress - Leandro F. Oliveira; Laís D. Rodrigues; Giancarlo M. Cardillo; Mariana B. Nejm; Marcia Guimarães-Marques; Selvin Z. Reyes-Garcia; Karolini Zuqui; Dalton V. Vassallo; Ana C. Fiorini; Carla A. Scorza; Fulvio A. Scorza (Environmental Science and Pollution Research, 2020)

WGEUROBUS – Working Group “Towards a EURopean OBservatory of the non-indigenous calanoid copepod Pseudodiaptomus marinUS” - M. Uttieri; L. Aguzzi; R. Aiese Cigliano; A. Amato; N. Bojanić; M. Brunetta; E. Camatti; Y. Carotenuto; T. Damjanović; F. Delpy; A. de Olazabal; I. Di Capua; et al. (Biological Invasions, 2020)

A novel cellular automata approach: seed input/output of the alien species Leucaena leucocephala in the soil and the effects of climate changes - Andréa Rodrigues Marques; Larissa Lopes Lima; Queila Souza Garcia; Allbens P. F. Atman (Plant Ecology, 2020)

GASMoC method: a phenol-free technique to detect acid-fast bacilli - A. Gomes; P. Amaral; R. Santos; S. Santos; F. Tortosa; P. Mendonça; A. Marques-Ramos (Histochemistry and Cell Biology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Molecular and biological characterization of a putative new sobemovirus infecting Physalis peruviana - Arnaldo Esquivel Fariña; Eduardo Silva Gorayeb; Viviana Marcela Camelo-García; Jaíne Bonin; Tatsuya Nagata; Joao Marcos F. Silva; Amauri Bogo; Jorge Alberto Marques Rezende; Fabio Nascimento da Silva; Elliot W. Kitajima (Archives of Virology, 2019)

Scoping Global Aquaculture Occupational Safety and Health - Lissandra Cavalli; Mohamed F. Jeebhay; Flavielle Marques; Rebecca Mitchell; Barbara Neis; Dorothy Ngajilo; Andrew Watterson (Journal of Agromedicine, 2019)

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Novel nonsense IL-12Rβ1 mutation associated with recurrent tuberculosis - Noor ul Akbar; Shahid Niaz Khan; Muhammad Usman Amin; Muhammad Ishfaq; Otavio Cabral-Marques; Lena F Schimke; Asif Iqbal; Ikram Ullah; Mubashir Hussain; Ijaz Ali; Nasar Khan; Nadia El Khawanky; et al. (Immunologic Research, 2019)

The role of strict nature reserves in protecting genetic diversity in a semiarid vegetation in Brazil - Emanuel M. Fonseca; Fernanda P. Werneck; Marcelo Gehara; Eliana F. Oliveira; Felipe de M. Magalhães; Flávia M. Lanna; Guilherme S. Lima; Ricardo Marques; Daniel O. Mesquita; Gabriel C. Costa; Guarino R. Colli; Adrian A. Garda (Biodiversity and Conservation, 2019)

New Molecular Markers Distinguishing Fonsecaea Agents of Chromoblastomycosis - Gabriela X. Schneider; Renata R. Gomes; Amanda Bombassaro; Kassiely Zamarchi; Morgana F. Voidaleski; Flávia F. Costa; Aniele C. R. Leão; Bruna J. F. S. Lima; Bruna S. Soley; Israella R. Colombo; Giovanna Z. Cândido; Mohammad J. Najafzadeh; et al. (Mycopathologia, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Spatial behaviour of Spanish Imperial Eagle Aquila adalberti juveniles during the dependence period revealed by high-resolution GPS tracking data - Rita F. Ramos; João P. Silva; Carlos Carrapato; Pedro Rocha; Paulo A. M. Marques; Jorge M. Palmeirim (Journal of Ornithology, 2019)

Regeneration of Diabetic Foot Ulcers Based on Therapy with Red LED Light and a Natural Latex Biomembrane - S. S. R. F. Rosa; M. F. F. Rosa; M. P. Marques; G. A. Guimarães; B. C. Motta; Y. C. L. Macedo; P. Inazawa; A. Dominguez; F. S. Macedo; C. A. P. Lopes; A. F. da Rocha (Annals of Biomedical Engineering, 2019)

The emerging pathogen of chestnut Gnomoniopsis castaneae: the challenge posed by a versatile fungus - G. Lione; R. Danti; P. Fernandez-Conradi; J. V. Ferreira-Cardoso; F. Lefort; G. Marques; J. B. Meyer; S. Prospero; L. Radócz; C. Robin; T. Turchetti; A. M. Vettraino; et al. (European Journal of Plant Pathology, 2019)

Evaluation of mercury phytoavailability in Oxisols - Francielle R. D. Lima; Mateus M. Engelhardt; Isabela C. F. Vasques; Gabriel C. Martins; Geraldo S. Cândido; Polyana Pereira; Rayner H. C. L. Reis; Aline O. Silva; Luiz Roberto G. Guilherme; João José Marques (Environmental Science and Pollution Research, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Synthesis, cytotoxic activity, and mode of action of new Santacruzamate A analogs - Silmara N. Andrade; Fernanda C. G. Evangelista; Diego Seckler; Deisielly R. Marques; Túlio R. Freitas; Renata R. Nunes; Júlia T. Oliveira; Rosy I. M. A. Ribeiro; Hélio B. Santos; Ralph G. Thomé; Alex G. Taranto; Fabio V. Santos; et al. (Medicinal Chemistry Research, 2018)

Diagnosis of Free and Convectively Coupled Equatorial Waves - Carlos A. F. Marques; José M. Castanheira (Mathematical Geosciences, 2018)

Aged rats are more vulnerable than adolescents to “ecstasy”-induced toxicity - R. Feio-Azevedo; V. M. Costa; D. J. Barbosa; A. Teixeira-Gomes; I. Pita; S. Gomes; F. C. Pereira; M. Duarte-Araújo; J. A. Duarte; F. Marques; E. Fernandes; M. L. Bastos; et al. (Archives of Toxicology, 2018)

Atorvastatin Prevents Early Oxidative Events and Modulates Inflammatory Mediators in the Striatum Following Intranasal 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) Administration in Rats - Naiani F. Marques; Adalberto A. Castro; Gianni Mancini; Fernanda L. Rocha; Adair R. S. Santos; Rui D. Prediger; Andreza Fabro De Bem; Carla I. Tasca (Neurotoxicity Research, 2018)

Toxin Gene Contents and Activity of Bacillus thuringiensis Strains Against Two Sugarcane Borer Species, Diatraea saccharalis (F.) and D. flavipennella (Box) - L M Silva; M C Silva; S M F A Silva; R C Alves; H A A Siqueira; E J Marques (Neotropical Entomology, 2018)

Brain-Defective Insulin Signaling Is Associated to Late Cognitive Impairment in Post-Septic Mice - Fernanda S. Neves; Patrícia T. Marques; Fernanda Barros‑Aragão; José Bruno Nunes; Aline M. Venancio; Danielle Cozachenco; Rudimar L. Frozza; Giselle F. Passos; Robson Costa; Jade de Oliveira; Daiane F. Engel; Andreza F. De Bem; et al. (Molecular Neurobiology, 2018)

Perturbation vectors to evaluate air quality using lichens and bromeliads: a Brazilian case study - F. Monna; A. N. Marques; R. Guillon; R. Losno; S. Couette; N. Navarro; G. Dongarra; E. Tamburo; D. Varrica; C. Chateau; F.O. Nepomuceno (Environmental Monitoring and Assessment, 2017)

Influence of estrous cycle hormonal fluctuations and gonadal hormones on the ventilatory response to hypoxia in female rats - Danuzia A. Marques; Débora de Carvalho; Glauber S. F. da Silva; Raphael E. Szawka; Janete A. Anselmo-Franci; Kênia C. Bícego; Luciane H. Gargaglioni (Pflügers Archiv - European Journal of Physiology, 2017)

The hnRNP Q-like gene is retroinserted into the B chromosomes of the cichlid fish Astatotilapia latifasciata - Bianca O. Carmello; Rafael L. B. Coan; Adauto L. Cardoso; Erica Ramos; Bruno E. A. Fantinatti; Diego F. Marques; Rogério A. Oliveira; Guilherme T. Valente; Cesar Martins (Chromosome Research, 2017)

Estimating synchronous demographic changes across populations using hABC and its application for a herpetological community from northeastern Brazil - Marcelo Gehara; Adrian A. Garda; Fernanda P. Werneck; Eliana F. Oliveira; Emanuel M. da Fonseca; Felipe Camurugi; Felipe de M. Magalhães; Flávia M. Lanna; Jack W. Sites; Ricardo Marques; Ricardo Silveira‐Filho; Vinícius A. São Pedro; et al. (Molecular Ecology, 2017)
Many studies propose that Quaternary climatic cycles contracted and/or expanded the ranges of species and biomes. Strong expansion–contraction dynamics of biomes presume concerted demographic changes of associated fauna. The analysis of temporal concordance of demographic changes can be used to test the influence of Quaternary climate on diversification processes. Hierarchical approximate Bayesian computation ( hABC ) is a powerful and flexible approach that models genetic data from multiple species, and can be used to estimate the temporal concordance of demographic processes. Using available single‐locus data, we can now perform large‐scale analyses, both in terms of number of species and geographic scope. Here, we first compared the power of four alternative hABC models for a collection of single‐locus data. We found that the model incorporating an a priori hypothesis about the timing of simultaneous demographic change had the best performance. Second, we applied the hABC models to a data set of seven squamate and four amphibian species occurring in the Seasonally Dry Tropical Forests (Caatinga) in northeastern Brazil, which, according to paleoclimatic evidence, experienced an increase in aridity during the Pleistocene. If this increase was important for the diversification of associated xeric‐adapted species, simultaneous population expansions should be evident at the community level. We found a strong signal of synchronous population expansion in the Late Pleistocene, supporting the increase of the Caatinga during this time. This expansion likely enhanced the formation of communities adapted to high aridity and seasonality and caused regional extirpation of taxa adapted to wet forest.

Synthesis, protease inhibition, and antileishmanial activity of new benzoxazoles derived from acetophenone or benzophenone and synthetic precursors - Laís R. S. Folquitto; Priscila F. Nogueira; Patrícia F. Espuri; Vanessa S. Gontijo; Thiago B. de Souza; Marcos J. Marques; Diogo T. Carvalho; Wagner A. S. Júdice; Danielle F. Dias (Medicinal Chemistry Research, 2017)

P transformations in cacao agroforests soils in the Atlantic forest region of Bahia, Brazil - S. Aleixo; A. C. Gama-Rodrigues; M. G. Costa; M. V. S. Sales; E. F. Gama-Rodrigues; J. R. B. Marques (Agroforestry Systems, 2017)

Hepatocyte spheroids as a competent in vitro system for drug biotransformation studies: nevirapine as a bioactivation case study - Pedro F. Pinheiro; Sofia A. Pereira; Shrika G. Harjivan; Inês L. Martins; Aline T. Marinho; Madalena Cipriano; Cristina C. Jacob; Nuno G. Oliveira; Matilde F. Castro; M. Matilde Marques; Alexandra M. M. Antunes; Joana P. Miranda (Archives of Toxicology, 2017)

Synthesis and in vitro evaluation of leishmanicidal activity of 7-hydroxy-4-phenylcoumarin derivatives - Isael A. Rosa; Letícia de Almeida; Karina F. Alves; Marcos J. Marques; Antônio M. Fregnan; Claudinei A. Silva; Juliana O. S. Giacoppo; Teodorico C. Ramalho; Diogo T. Carvalho; Marcelo H. dos Santos (Medicinal Chemistry Research, 2017)

Synthesis and in vitro evaluation of novel triazole/azide chalcones - Fernanda C. G. Evangelista; Maralice O. Bandeira; Graziele D. Silva; Marina G. Silva; Silmara N. Andrade; Deisielly R. Marques; Luciana M. Silva; Whocely V. Castro; Fabio V. Santos; Gustavo H. R. Viana; José A. F. P. Villar; Adriano P. Sabino; et al. (Medicinal Chemistry Research, 2017)

Genetic divergence among invasive and native populations of the yellow peacock cichlid Cichla kelberi - A. C. P. B. Marques; A. C. S. Franco; F. Salgueiro; E. García‐Berthou; L. N. Santos (Journal of Fish Biology, 2016)
This study used the hypervariable domain of the mitochondrial DNA ( mtDNA ) control region ( CR ) to assess the genetic divergence among native and invasive populations of Cichla kelberi , which is considered the first peacock cichlid introduced and established throughout Brazil and is among the most invasive populations of this genus worldwide. The maximum likelihood tree based on 53 CR sequences with strong bootstrap support revealed that C. kelberi forms a monophyletic clade, confirming that all 30 C. kelberi studied belong to this morphotype. Additionally, the haplotype analysis of the C. kelberi sequences from 11 sampling sites revealed that invasive populations are much less diverse than native ones and largely dominated by a single haplotype that prevailed in reservoirs at the Paraíba do Sul River basin. Two haplotypes were recorded exclusively in an invasive population at Porto Rico, southern Brazil, and one private haplotype was detected in two reservoirs from Paraíba do Sul (Pereira Passos and Paracambi), suggesting more than one introduction event and that native populations should be better evaluated to encompass the entire genetic diversity of native C. kelberi . The possible route and pathways of C. kelberi introduction are also briefly discussed.

Assessing the conservation status of Mediterranean temporary ponds using biodiversity: a new tool for practitioners - A. Lumbreras; J. T. Marques; A. F. Belo; M. Cristo; M. Fernandes; D. Galioto; M. Machado; A. Mira; P. Sá-Sousa; R. Silva; L. G. Sousa; C. Pinto-Cruz (Hydrobiologia, 2016)

Variability on microevolutionary and macroevolutionary scales: a review on patterns of morphological variation in Cnidaria Medusozoa - Amanda F. Cunha; Maximiliano M. Maronna; Antonio C. Marques (Organisms Diversity & Evolution, 2016)

Multicriteria analysis applied to landslide susceptibility mapping - Juliana F. Lorentz; Maria Lucia Calijuri; Eduardo Gomes Marques; Alessandra Carreiro Baptista (Natural Hazards, 2016)

Performance of the L2C civil GPS signal under various ionospheric scintillation effects - H. A. S. Marques; J. F. G. Monico; H. A. Marques (GPS Solutions, 2016)

Myelin Lipids Inhibit Axon Regeneration Following Spinal Cord Injury: a Novel Perspective for Therapy - Fernando M. Mar; Tiago F. da Silva; Marlene M. Morgado; Lorena G. Rodrigues; Daniel Rodrigues; Marta I. L. Pereira; Ana Marques; Vera F. Sousa; João Coentro; Clara Sá-Miranda; Mónica M. Sousa; Pedro Brites (Molecular Neurobiology, 2016)

Emergy analysis of a silvo-pastoral system, a case study in southern Portugal - Ana Margarida P. Fonseca; Carlos A. F. Marques; Teresa Pinto-Correia; Daniel E. Campbell (Agroforestry Systems, 2016)

Influence of landscape heterogeneity and meteorological features on small mammal abundance and richness in a coastal wetland system, NW Portugal - Sara F. Marques; Rita G. Rocha; Eduardo S. Mendes; Carlos Fonseca; Joaquim P. Ferreira (European Journal of Wildlife Research, 2015)

Multiple stage recruitment limitation and density dependence effects in two tropical forests - Marcia C. M. Marques; David F. R. P. Burslem (Plant Ecology, 2015)

How much do we know about the endangered Atlantic Forest? Reviewing nearly 70 years of information on tree community surveys - Renato A. F. de Lima; Danilo P. Mori; Gregory Pitta; Melina O. Melito; Carolina Bello; Luiz F. Magnago; Victor P. Zwiener; Daniel D. Saraiva; Márcia C. M. Marques; Alexandre A. de Oliveira; Paulo I. Prado (Biodiversity and Conservation, 2015)

Unraveling the interactive effects of climate change and oil contamination on laboratory‐simulated estuarine benthic communities - Francisco J. R. C. Coelho; Daniel F. R. Cleary; Rui J. M. Rocha; Ricardo Calado; José M. Castanheira; Sílvia M. Rocha; Artur M. S. Silva; Mário M. Q. Simões; Vanessa Oliveira; Ana I. Lillebø; Adelaide Almeida; Ângela Cunha; et al. (Global Change Biology, 2015)
There is growing concern that modifications to the global environment such as ocean acidification and increased ultraviolet radiation may interact with anthropogenic pollutants to adversely affect the future marine environment. Despite this, little is known about the nature of the potential risks posed by such interactions. Here, we performed a multifactorial microcosm experiment to assess the impact of ocean acidification, ultraviolet B (UV‐B) radiation and oil hydrocarbon contamination on sediment chemistry, the microbial community (composition and function) and biochemical marker response of selected indicator species. We found that increased ocean acidification and oil contamination in the absence of UV‐B will significantly alter bacterial composition by, among other things, greatly reducing the relative abundance of Desulfobacterales , known to be important oil hydrocarbon degraders. Along with changes in bacterial composition, we identified concomitant shifts in the composition of oil hydrocarbons in the sediment and an increase in oxidative stress effects on our indicator species. Interestingly, our study identifies UV‐B as a critical component in the interaction between these factors, as its presence alleviates harmful effects caused by the combination of reduced pH and oil pollution. The model system used here shows that the interactive effect of reduced pH and oil contamination can adversely affect the structure and functioning of sediment benthic communities, with the potential to exacerbate the toxicity of oil hydrocarbons in marine ecosystems.

Environmental cues during overland dispersal by three freshwater invaders: Eriocheir sinensis, Pacifastacus leniusculus, and Procambarus clarkii (Crustacea, Decapoda) - M. Marques; F. Banha; M. Águas; P. Anastácio (Hydrobiologia, 2015)

Hsp70 expression in shrimp Litopenaeus vannamei in response to IHHNV and WSSV infection - Pedro A. Valentim-Neto; Juliana R. Moser; Ana P. M. Fraga; Maria R. F. Marques (VirusDisease, 2014)

Association of IgG immunoglobulin and subclasses level with the severity of chromoblastomycosis due to Fonsecaea pedrosoi and therapeutic response to itraconazole - C. d. M. P. e Silva de Azevedo; O. Bruña-Romero; S. G. Marques; F. R. F. do Nascimento; M. C. Pinto; L. A. Silva; L. É. M. Bouillet; F. S. de Azevedo; M. A. de Resende Stoianoff (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Differential expression of proteins in the gills of Litopenaeus vannamei infected with white spot syndrome virus - Pedro A. Valentim-Neto; Ana P. M. Fraga; Maria R. F. Marques (Aquaculture International, 2014)

Genetic divergence and evidence for sympatric host-races in the highly polyphagous brown tail moth, Euproctis chrysorrhoea (Lepidoptera: Erebidae) - Joana F. Marques; Hong-Lei Wang; Glenn P. Svensson; Enric Frago; Olle Anderbrant (Evolutionary Ecology, 2014)

Evaluation of muscle force classification using shape analysis of the sEMG probability density function: a simulation study - F. S. Ayachi; S. Boudaoud; C. Marque (Medical & Biological Engineering & Computing, 2014)

Sampling plans for pest mites on physic nut - Jander F. Rosado; Renato A. Sarmento; Marçal Pedro-Neto; Tarcísio V. S. Galdino; Renata V. Marques; Eduardo A. L. Erasmo; Marcelo C. Picanço (Experimental and Applied Acarology, 2014)

A mosaic of opportunities? Spatio-temporal patterns of bat diversity and activity in a strongly humanized Mediterranean wetland - Eduardo S. Mendes; Maria João Ramos Pereira; Sara F. Marques; Carlos Fonseca (European Journal of Wildlife Research, 2014)

Grazing behaviour of a non‐herbivorous characin: revisiting plasticity - P. S. Marques; M. F. Costa; C. C. D. Corrêa; M. M. Marinho; R. Mazzoni (Journal of Fish Biology, 2014)
Feeding behaviour and diet of Bryconamericus microcephalus differed between canopy conditions. At the open canopy site, a behavioural modification, grazing on algae, was observed. This was also reflected in gut content analysis and suggests behavioural plasticity in response to resource availability.

Are seed germination and ecological breadth associated? Testing the regeneration niche hypothesis with bromeliads in a heterogeneous neotropical montane vegetation - Andréa Rodrigues Marques; Allbens P. F. Atman; Fernando A. O. Silveira; José Pires de Lemos-Filho (Plant Ecology, 2014)

Changes in the normal mode energetics of the general atmospheric circulation in a warmer climate - C. A. F. Marques; J. M. Castanheira; A. Rocha (Climate Dynamics, 2014)

Environmental effects of anticholinesterasic therapeutic drugs on a crustacean species, Daphnia magna - R. Rocha; F. Gonçalves; C. Marques; B. Nunes (Environmental Science and Pollution Research, 2014)

Cisplatin associated with LY294002 increases cytotoxicity and induces changes in transcript profiles of glioblastoma cells - P. O. Carminati; F. S. Donaires; M. M. Marques; E. A. Donadi; G. A. S. Passos; E. T. Sakamoto-Hojo (Molecular Biology Reports, 2014)

Structure Activity Relationships in Alkylammonium C12-Gemini Surfactants Used as Dermal Permeation Enhancers - Sérgio M. C. Silva; João J. S. Sousa; Eduardo F. Marques; Alberto A. C. C. Pais; Bozena B. Michniak-Kohn (The AAPS Journal, 2013)

Mini-Winkler Extractor and Pitfall Trap as Complementary Methods to Sample Formicidae - F H O Silva; J H C Delabie; G B dos Santos; E Meurer; M I Marques (Neotropical Entomology, 2013)

Performance evaluation of retrofitting strategies for non-seismically designed RC buildings using steel braces - H. Varum; F. Teixeira-Dias; P. Marques; A. V. Pinto; A. Q. Bhatti (Bulletin of Earthquake Engineering, 2013)

Development and validation of an experimental life support system for assessing the effects of global climate change and environmental contamination on estuarine and coastal marine benthic communities - Francisco J. R. C. Coelho; Rui J. M. Rocha; Ana C. C. Pires; Bruno Ladeiro; José M. Castanheira; Rodrigo Costa; Adelaide Almeida; Ângela Cunha; Ana Isabel Lillebø; Rui Ribeiro; Ruth Pereira; Isabel Lopes; et al. (Global Change Biology, 2013)
An experimental life support system ( ELSS ) was constructed to study the interactive effects of multiple stressors on coastal and estuarine benthic communities, specifically perturbations driven by global climate change and anthropogenic environmental contamination. The ELSS allows researchers to control salinity, pH , temperature, ultraviolet radiation ( UVR ), tidal rhythms and exposure to selected contaminants. Unlike most microcosms previously described, our system enables true independent replication (including randomization). In addition to this, it can be assembled using commercially available materials and equipment, thereby facilitating the replication of identical experimental setups in different geographical locations. Here, we validate the reproducibility and environmental quality of the system by comparing chemical and biological parameters recorded in our ELSS with those prevalent in the natural environment. Water, sediment microbial community and ragworm (the polychaete Hediste diversicolor ) samples were obtained from four microcosms after 57 days of operation. In general, average concentrations of dissolved inorganic nutrients ( NO 3 − ; NH 4 + and PO 4 −3 ) in the water column of the ELSS experimental control units were within the range of concentrations recorded in the natural environment. While some shifts in bacterial community composition were observed between in situ and ELSS sediment samples, the relative abundance of most metabolically active bacterial taxa appeared to be stable. In addition, ELSS operation did not significantly affect survival, oxidative stress and neurological biomarkers of the model organism Hediste diversicolor . The validation data indicate that this system can be used to assess independent or interactive effects of climate change and environmental contamination on benthic communities. Researchers will be able to simulate the effects of these stressors on processes driven by microbial communities, sediment and seawater chemistry and to evaluate potential consequences to sediment toxicity using model organisms such as Hediste diversicolor .

Association of microparticles and preeclampsia - Fabiana K. Marques; Fernanda M. F. Campos; Lirlândia P. Sousa; Andréa Teixeira-Carvalho; Luci M. S. Dusse; Karina B. Gomes (Molecular Biology Reports, 2013)

Cellular and humoral immune responses of S enegalese sole, S olea senegalensis ( K aup), following challenge with two P hotobacterium damselae subsp. piscicida strains from different geographical origins - B Costas; P C N P Rêgo; I Simões; J F Marques; M Castro‐Cunha; A Afonso (Journal of Fish Diseases, 2013)
The present study aimed to investigate leucocyte responses to inflammation as well as some innate immune parameters of S enegalese sole, S olea senegalensis , following challenge with two strains of P hotobacterium damselae subsp. piscicida belonging to the E uropean and J apanese clones described for this bacterium. Pathogenicity assays were performed to assess the virulence of each P hotobacterium damselae subsp. piscicida strain for sole. Subsequently, fish were intraperitoneally injected with phosphate‐buffered saline (control) or two concentrations (2 × 10 2 and 2 × 10 6 CFU mL −1 ) of each bacterial strain and sampled after 6 and 24 h. Results showed that the E uropean isolate induces a higher degree of response than the J apanese strain. While blood neutrophilia and monocytosis correlated well with the increase in neutrophil and macrophage numbers in the peritoneal cavity, fish infected with the E uropean isolate presented higher peritoneal cell numbers than fish challenged with the J apanese strain. In addition, alternative complement pathway activity and respiratory burst of head kidney leucocytes increased significantly in fish infected with the E uropean isolate. The enhanced innate immune response displayed by S enegalese sole challenged with the E uropean isolate is probably due to the higher degree of virulence presented by this P hotobacterium damselae subsp. piscicida strain.

Antifolates inhibit Cryptococcus biofilms and enhance susceptibility of planktonic cells to amphotericin B - R. Aguiar Cordeiro; C. I. Mourão; M. F. G. Rocha; F. J. Farias Marques; C. E. C. Teixeira; D. F. Oliveira Miranda; L. V. P. Neto; R. S. N. Brilhante; T. Jesus Pinheiro Gomes Bandeira; J. J. C. Sidrim (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Intracellular mechanisms of hydroquinone toxicity on endotoxin-activated neutrophils - Cristina Bichels Hebeda; Fernanda Júdice Pinedo; Simone Marques Bolonheis; Zulma F. Ferreira; Marcelo Nicolas Muscará; Simone Aparecida Teixeira; Sandra Helena Poliselli Farsky (Archives of Toxicology, 2012)

Selective geochemistry of iron in mangrove soils in a semiarid tropical climate: effects of the burrowing activity of the crabs Ucides cordatus and Uca maracoani - J. M. C. Araújo; X. L. Otero; A. G. B. Marques; G. N. Nóbrega; J. R. F. Silva; T. O. Ferreira (Geo-Marine Letters, 2012)

Stem growth and phenology of two tropical trees in contrasting soil conditions - F. C. G. Cardoso; R. Marques; P. C. Botosso; M. C. M. Marques (Plant and Soil, 2012)

Ecotoxicological effects of ciprofloxacin on freshwater species: data integration and derivation of toxicity thresholds for risk assessment - N. Martins; R. Pereira; N. Abrantes; J. Pereira; F. Gonçalves; C. R. Marques (Ecotoxicology, 2012)

Role of Methylmercury Exposure (from Fish Consumption) on Growth and Neurodevelopment of Children Under 5 Years of Age Living in a Transitioning (Tin-Mining) Area of the Western Amazon, Brazil - Rejane C. Marques; José G. Dórea; Renata S. Leão; Verusca G. dos Santos; Lucélia Bueno; Rayson C. Marques; Katiane G. Brandão; Elisabete F. A. Palermo; Jean Remy D. Guimarães (Archives of Environmental Contamination and Toxicology, 2012)

An enterprise architecture approach to forest management support systems design: an application to pulpwood supply management in Portugal - A. F. Marques; J. G. Borges; P. Sousa; A. M. Pinho (European Journal of Forest Research, 2011)

Soil apparent electrical conductivity and geographically weighted regression for mapping soil - J. M. Terrón; J. R. Marques da Silva; F. J. Moral; Alfonso García-Ferrer (Precision Agriculture, 2011)

Characterization of wildfires in Portugal - S. Marques; J. G. Borges; J. Garcia-Gonzalo; F. Moreira; J. M. B. Carreiras; M. M. Oliveira; A. Cantarinha; B. Botequim; J. M. C. Pereira (European Journal of Forest Research, 2011)

RINEX_HO: second- and third-order ionospheric corrections for RINEX observation files - H. A. Marques; J. F. G. Monico; M. Aquino (GPS Solutions, 2011)

Global diagnostic energetics of five state-of-the-art climate models - C. A. F. Marques; A. Rocha; J. Corte-Real (Climate Dynamics, 2011)

Management of chestnut plantations for a multifunctional land use under Mediterranean conditions: effects on productivity and sustainability - A. Martins; G. Marques; O. Borges; E. Portela; J. Lousada; F. Raimundo; M. Madeira (Agroforestry Systems, 2011)

The role of geosciences in the assessment of low-temperature geothermal resources (N-Portugal): a review - José M. Marques; P. M. Carreira; J. E. Marques; H. I. Chaminé; P. E. Fonseca; F. A. Monteiro Santos; H. G. M. Eggenkamp; J. Teixeira (Geosciences Journal, 2010)

Mycobiota and Ochratoxin A in laboratory mice feed: preliminary study - Inês Almeida; H. Marina Martins; Marta F. Marques; Salomé Magalhães; Fernando Bernardo (Veterinary Research Communications, 2010)

Improving the GNSS positioning stochastic model in the presence of ionospheric scintillation - M. Aquino; J. F. G. Monico; A. H. Dodson; H. Marques; G. De Franceschi; L. Alfonsi; V. Romano; M. Andreotti (Journal of Geodesy, 2009)

Characterization of Desmodesmus pleiomorphus isolated from a heavy metal-contaminated site: biosorption of zinc - Cristina M. Monteiro; Ana P. G. C. Marques; Paula M. L. Castro; F. Xavier Malcata (Biodegradation, 2009)

Non-volant mammalian diversity in fragments in extreme eastern Amazonia - Anita I. Stone; Eldianne M. Lima; G. F. S. Aguiar; Carolina C. Camargo; Tamara A. Flores; Douglas A. Kelt; Suely A. Marques-Aguiar; João A. L. Queiroz; Rossano M. Ramos; José S. Silva Júnior (Biodiversity and Conservation, 2009)

Global atmospheric energetics from NCEP–Reanalysis 2 and ECMWF–ERA40 Reanalysis - Carlos A. F. Marques; Alfredo Rocha; João Corte‐Real; José M. Castanheira; Juan Ferreira; Paulo Melo‐Gonçalves (International Journal of Climatology, 2009)
The global atmospheric energy cycle is estimated on an annual basis using Reanalysis 2 data from the National Centers for Environmental Prediction and National Center for Atmospheric Research (NCEP/NCAR), and ERA 40 Reanalyses from the European Centre for Medium‐Range Weather Forecasts (ECMWF) for the period 1979–2001. A formalism to avoid belowground data on pressure levels intercepted by topography is adopted. No appreciable differences were found between the two datasets from the energetics point of view. The so‐called ωα and v ·grad z formulations were both used for the conversions from zonal available potential energy into zonal kinetic energy ( C Z ) and from eddy available potential energy into eddy kinetic energy ( C E ). Results with both formulations are comparable only when using the formalism preventing belowground data to enter into the computations. Atmospheric energetics are also computed using ECMWF Reanalyses for the period 1958–1978. A significant increase was found in the eddy kinetic and eddy available potential energies from the early period to the later period, likely related to the assimilation in the reanalyses of satellite data after 1979. The conversion rate, C Z , was found to change its sign throughout the years. The atmospheric energy cycle using the ECMWF Reanalyses data is compared with five previous estimates. Differences in the direction of the conversion rate, C Z , between the various estimates may be explained by the different time periods chosen for averaging. Owing to the omission of belowground data, the conversion from zonal available potential energy into eddy available potential energy ( C A ) was somewhat smaller in ECMWF Reanalyses than in the previous estimates. Despite those differences, an overall agreement may be found between the various estimates for the atmospheric energy cycle. Copyright © 2008 Royal Meteorological Society

Effect of hydrogen peroxide on secretory response, calcium mobilisation and caspase-3 activity in the isolated rat parotid gland - António Mata; Duarte Marques; María A. Martínez-Burgos; João Silveira; Joana Marques; Maria F. Mesquita; José A. Pariente; Gines M. Salido; Jaipaul Singh (Molecular and Cellular Biochemistry, 2008)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

A new species of Potamotrygonocestus Brooks & Thorson, 1976 (Eucestoda: Tetraphyllidea) from Plesiotrygon iwamae Rosa, Castello & Thorson (Mylliobatoidea: Potamotrygonidae) and a redescription of Potamotrygonocestus chaoi Marques, Brooks & Araujo, 2003 - N. M. Luchetti; F. P. L. Marques; P. Charvet-Almeida (Systematic Parasitology, 2008)

Evaluation of the maize (Zea mays L.) diversity on the Archipelago of Madeira - Miguel Ângelo A. Pinheiro de Carvalho; José Filipe Teixeira Ganança; Ivo Abreu; Nélia F. Sousa; Teresa M. Marques dos Santos; Maria Rita Clemente Vieira; Mario Motto (Genetic Resources and Crop Evolution, 2008)

Role of σ54 in the regulation of genes involved in type I and type IV pili biogenesis in Xylella fastidiosa - José F. da Silva Neto; Tie Koide; Cecília M. Abe; Suely L. Gomes; Marilis V. Marques (Archives of Microbiology, 2008)

Sildenafil citrate concentrations not affecting oxidative phosphorylation depress H2O2 generation by rat heart mitochondria - Maria A. S. Fernandes; Ricardo J. F. Marques; Joaquim A. F. Vicente; Maria S. Santos; Pedro Monteiro; António J. M. Moreno; José B. A. Custódio (Molecular and Cellular Biochemistry, 2008)

Taxonomic Impediment or Impediment to Taxonomy? A Commentary on Systematics and the Cybertaxonomic-Automation Paradigm - Marcelo R. de Carvalho; Flávio A. Bockmann; Dalton S. Amorim; Carlos Roberto F. Brandão; Mário de Vivo; José L. de Figueiredo; Heraldo A. Britski; Mário C. C. de Pinna; Naércio A. Menezes; Fernando P. L. Marques; Nelson Papavero; Eliana M. Cancello; et al. (Evolutionary Biology, 2007)

Magnesium–calcium signalling in rat parotid acinar cells: effects of acetylcholine - Antonio Mata; Duarte Marques; María A. Martínez-Burgos; João Silveira; Joana Marques; Maria F. Mesquita; José A. Pariente; Gines M. Salido; Jaipaul Singh (Molecular and Cellular Biochemistry, 2007)

Monitoring of coastal and transitional waters under the E.U. Water Framework Directive - J. G. Ferreira; C. Vale; C. V. Soares; F. Salas; P. E. Stacey; S. B. Bricker; M. C. Silva; J. C. Marques (Environmental Monitoring and Assessment, 2007)

Applicability of ecological evaluation tools in estuarine ecosystems: the case of the lower Mondego estuary (Portugal) - H. Teixeira; F. Salas; M. A. Pardal; J. C. Marques (Hydrobiologia, 2007)

Zooplankton distribution and dynamics in a temperate shallow estuary - Sónia Cotrim Marques; M. A. Pardal; M. J. Pereira; F. Gonçalves; J. C. Marques; U. M. Azeiteiro (Hydrobiologia, 2007)

The chloroxoquinolinic derivative 6-chloro-1,4-dihydro-4-oxo-1-(β-D-ribofuranosyl) quinoline-3-carboxylic acid inhibits HSV-1 adsorption by impairing its adsorption on HVEM - T. M. L. Souza; M. C. Bastos V. De Souza; V. F. Ferreira; C. V. B. Santos Canuto; I. Pereira Marques; C. F. L. Fontes; I. C. P. P. Frugulhetti (Archives of Virology, 2007)

Comparison of Solea solea macroparasites between two nursery‐continental shelf systems in the Bay of Biscay and the Portuguese coast - E. D. H. Durieux; J. F. Marques; P. Sasal; M‐L. Bégout; H. N. Cabral (Journal of Fish Biology, 2007)
Digenean metacercariae of 0 year group common sole Solea solea ( n = 70) were more abundant in the embayed nursery of the Pertuis Charentais than in the Tagus estuary nursery. Macroparasite assemblages of adult sole ( n = 119) displayed only one species in common between the Bay of Biscay and the Portuguese coast continental shelves. These data highlighted the potential use of macroparasites as biological tags in various aspects of common sole ecology.

Seasonal variation of sound production in the Lusitanian toadfish Halobatrachus didactylus - M. C. P. Amorim; R. O. Vasconcelos; J. F. Marques; F. Almada (Journal of Fish Biology, 2006)
Seasonal variation of sound production, which includes boatwhistles, grunts, croaks and double croaks, was studied in the Lusitanian toadfish Halobatrachus didactylus . Boatwhistles were emitted during the mating season in contrast with the other sound types, which were emitted all year round.

Soleidae macroparasites along the Portuguese coast: latitudinal variation and host–parasite associations - J. F. Marques; M. J. Santos; H. N. Cabral (Marine Biology, 2006)

Absence of DNA Damage in Multiple Organs after Oral Exposure to Fluoride in Wistar Rats - M. A. R. Buzalaf; D. M. F. Salvadori; M. E. A. Marques; E. E. Caroselli; A. L. Leite; E. A. Camargo; D. A. Ribeiro (Bulletin of Environmental Contamination and Toxicology, 2006)

Expression of cell cycle regulatory proteins in epithelial components of dental follicles - Mariza A. Matsumoto; Hugo Nary Filho; Francine M. Jorge; Daisy M. F. Salvadori; Mariângela E. A. Marques; Daniel A. Ribeiro (Journal of Molecular Histology, 2006)

Mineralogy, geochemistry, and Nd isotope composition of the Rainbow hydrothermal field, Mid-Atlantic Ridge - A. F. A. Marques; F. Barriga; V. Chavagnac; Y. Fouquet (Mineralium Deposita, 2006)

Methodology for hypoglycaemia detection based on the processing, analysis and classification of the electroencephalogram - F. Laione; J. L. B. Marques (Medical & Biological Engineering & Computing, 2005)

Ticks (Acari: Ixodida) on wild carnivores in Brazil - Marcelo B. Labruna; Rodrigo S. P. Jorge; Dênis A. Sana; Anah Tereza A. Jácomo; Cyntia K. Kashivakura; Mariana M. Furtado; Claudia Ferro; Samuel A. Perez; Leandro Silveira; Tarcísio S. Santos JR; Samuel R. Marques; Ronaldo G. Morato; et al. (Experimental and Applied Acarology, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Lanthanum Effect on the Dynamics of Tight Junction Opening and Closing - F. Lacaz-Vieira; M. M. Marques (The Journal of Membrane Biology, 2004)

Effects of diabetes mellitus on salivary secretion and its composition in the human - Antonio D. Mata; Duarte Marques; Sara Rocha; Helena Francisco; Carolina Santos; Maria F. Mesquita; Jaipaul Singh (Molecular and Cellular Biochemistry, 2004)

Multi-criteria analysis for the identification of waste disposal areas - Maria Lúcia Calijuri; Eder T. Marques; Juliana F. Lorentz; Roberto F. Azevedo; Carlos A. B. Carvalho (Geotechnical and Geological Engineering, 2004)

Insertional Transposon Mutagenesis in the Xylella fastidiosa Citrus Variegated Chlorosis Strain with Transposome - Tie Koide; Jos F. da Silva Neto; Suely L. Gomes; Marilis V. Marques (Current Microbiology, 2004)

Selection of Priority Areas for Fish Conservation in Guadiana River Basin, Iberian Peninsula - A. F. FILIPE; T. A. MARQUES; S. SEABRA; P. TIAGO; F. RIBEIRO; L. MOREIRA DA COSTA; I. G. COWX; M. J. COLLARES‐PEREIRA (Conservation Biology, 2004)
We developed a species‐by‐species approach for selecting protected areas for conservation of native freshwater fishes in semiarid regions, with catchment as the fundamental landscape unit for conservation efforts. Input data were composed of occurrences of freshwater fishes and landscape variables, and general quantification of occurrence, abundance, and endemicity of each fish species, to derive an index of conservation value for each species. Probability of occurrence of each species was performed with logistic‐regression analysis based on the landscape variables and extrapolated to the entire study area with a geographic information system. We estimated the conservation value of a stream reach by summing the predicted probability of occurrence of each species multiplied by its corresponding conservation value. To define and select reserves, we used a threshold that maximizes conservation value of the stream reaches but identifies the minimum number of reaches for protection. The approach was applied to native freshwater fishes in the Guadiana River basin (southern Iberian Peninsula), which are threatened by the construction of two major dams. We used the data from 1 sampling year (1999) to produce the models, which were validated based on data collected in 2000 and 2001. We used variables of climate (3), geomorphology (4), hydrology (7), and human influence (6) to build the predictive models, which revealed that native species occur over a wide range of riverine habitats, with stream order and location in the basin the most frequently selected variables. The conservation value of species varied considerably, with Anaecypris hispanica the highest‐ranked species. The catchments selected for reserves were the mainstream of the Guadiana River (upstream and downstream of the Alqueva and Pedrogão reservoirs) and the Degebe, Ardila, and Enxoé catchments. Our approach is a pragmatic way to address the urgent need to protect Guadiana native fish species in light of the ongoing anthropogenic degradation of aquatic environments.

Pulses of Cell Ca 2+ and the Dynamics of Tight Junction Opening and Closing - F. Lacaz-Vieira; M. M. Marques (The Journal of Membrane Biology, 2003)

Landslide activity in Upper Palaeozoic shale sea cliffs: a case study along the western coast of the Algarve (Portugal) - Fernando M. S. F. Marques (Bulletin of Engineering Geology and the Environment, 2003)

Redox modulation of reductase and phosphatase activities in human erythrocytes - F. Marques; M. E. Crespo; Z. I. Silva; M. Bicho (Protoplasma, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Serological behaviour of isolated African Swine fever virus - J. D. Vigrio; A. M. Terrinha; A. L. Bastos; J. F. Moura-Nunes; Dante Marques; J. F. Silva (Archives of Virology, 1970)

An autoradiographic and immunofluorescent study of the infectious cycle of sheeppox virus in cell cultures exposed to 5-fluorodeoxyuridine - J. Vigário; A. Terrinha; J. Nunes; A. Bastos; D. Marques; D. Correia; F. Silva (Archives of Virology, 1968)